Dental filling and restorative material and kit containing the same
By using organic fluorinating agents and ion-release glass in tooth filling and restoration materials, combining the role of both, the problem of aesthetics and strength reduction of existing materials when improving the dental strengthening ability is solved, and the tooth filling and repair effect with high strengthening ability, excellent aesthetics and strength is achieved.
Patent Information
- Application Number
- JP2023186792
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-10-31
- Publication Date
- 2025-05-15
AI Technical Summary
When existing dental filling and restoration materials use metal fluoride salts as the source of continuous release of fluorine, the continuous release of fluorine is low, resulting in insufficient dental strengthening ability. At the same time, when the release amount is increased to improve strengthening ability, the aesthetics and strength will decrease, making it difficult to effectively improve the strengthening ability of the tooth texture.
The tooth filling and repair material combined with organic fluorinating agent and ion sustained release glass is used to obtain the ability to strengthen teeth through the combined action of organic fluorinating agent and ion sustained release glass, while maintaining the aesthetics and strength of the material.
It realizes high strengthening capabilities of tooth filling and restoration materials, while maintaining the excellent aesthetics and strength of the materials, solving the problem of the aesthetics and strength of existing materials when improving the dental strengthening capabilities.
Smart Images

Figure 2025075546000001 
Figure 2025075546000002 
Figure 2025075546000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a dental filling and restorative material and a kit comprising the same. [Background technology]
[0002] In the past, it has been proposed to incorporate an inorganic fluoride compound as a fluoride sustained release source into dental filling and restorative materials in order to strengthen tooth structure. It is known that metal fluoride salt is used as the inorganic fluorine compound.However, when metal fluoride salt is mixed into dental filling and restorative materials, the amount of fluoride released is generally low, and the tooth structure strengthening ability brought about by this is insufficient.In addition, when metal fluoride salt is mixed into dental filling and restorative materials in a large amount in order to increase the amount of fluoride released, the aesthetics and strength of the material after dissolution are reduced, so that the tooth structure strengthening ability cannot be sufficiently improved. It is also known that fluorine-containing ion-releasing glass is blended into dental filling and restorative materials as the above-mentioned fluorine-releasing source. For example, Patent Document 1 describes a dental composition containing an inorganic filler in which inorganic particles made of fluorine-containing glass are provided with a predetermined coating layer. However, in order to ensure sufficient fluidity of dental filling and restorative materials, the blending amount of ion-releasing glass is limited, and it is still difficult to increase the blending amount of ion-releasing glass to increase the amount of fluorine released and thereby improve the tooth structure strengthening ability. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2001-139844 A Summary of the Invention [Problem to be solved by the invention]
[0004] Thus, conventional dental filling and restorative materials that use inorganic fluorine compounds, such as metal fluorides or fluorine-containing ion-releasing glass, as a fluoride-releasing source have the problem that they are unable to further enhance the tooth structure strengthening ability while maintaining the properties required of dental filling and restorative materials, such as aesthetics and strength. Therefore, an object of the present invention is to provide a novel and useful dental filling and restorative material that can give a hardened product having high tooth structure strengthening ability while ensuring aesthetics and strength. [Means for solving the problem]
[0005] As a result of various investigations, the inventors have found that a hardened material having high tooth structure strengthening ability, aesthetics and strength can be obtained by combining an organic fluorinating agent with an ion-releasing glass, and have arrived at the present invention. That is, the present invention encompasses the following inventions. [1] A dental filling and restorative material comprising an organic fluorinating agent (A), an ion-releasing glass (B), and a polymerizable monomer (C). [2] A dental filling and restoring material as described in [1] above, which does not contain a solvent or further contains a solvent, and the mass of the solvent is more than 0 parts by mass and not more than 1.0 parts by mass per 100 parts by mass of the total mass of the dental filling and restoring material. [3] The dental filling and restoring material according to the above [1] or [2], wherein the organic fluorinating agent (A) contains at least one element selected from the group consisting of nitrogen, phosphorus, boron, sulfur, and iodine. [4] The organic fluorinating agent (A) is selected from the group consisting of tetramethylammonium fluoride, tetraethylammonium fluoride, tetrabutylammonium fluoride, tetrabutylammonium difluorotriphenyltin, tetrabutylammonium difluorotriphenylsilicate, pyrimidine-2-sulfonyl fluoride, pyridine-2-sulfonyl fluoride, 2-chloro-1,3-bis(2,6-diisopropylphenyl)-1H-imidazolium chloride-cesium fluoride, perfluoro-1-butanesulfonyl fluoride, morpholinosulfur trifluoride, hexafluoropropene diethylamine, and 2-fluoro-1-methylpyridinium. The dental filling and restorative material according to any one of the above [1] to [3], which is at least one compound selected from the group consisting of p-toluenesulfonate; (diethylamino)sulfur trifluoride; 4-tert-butyl-2,6-dimethylphenylsulfur trifluoride; bis(2-methoxyethyl)aminosulfur trifluoride; 1,3-bis(2,6-diisopropylphenyl)-2-fluoroimidazolium tetrafluoroborate; 1-fluoropyridinium trifluoromethanesulfonate; 1,1'-difluoro-2,2'-bipyridinium bis(tetrafluoroborate); 1-fluoro-2,4,6-trimethylpyridinium tetrafluoroborate; 1-fluoro-3,3-dimethyl-1,2-benzoiodoxole; N-fluoro-N'-(chloromethyl)triethylenediamine bis(tetrafluoroborate); N-fluorobenzenesulfonimide; and salts thereof. [5] The dental filling and restoring material according to any one of the above [1] to [4], wherein the polymerizable monomer (C) comprises a (meth)acrylic compound (c-1) having at least one group or bond selected from the group consisting of a hydroxyl group, a carboxylic acid group, an amino group, an amide group, and a urethane bond. [6] The dental filling and restoring material according to the above [5], wherein the mass of the organic fluorinating agent (A) is 0.005 to 30 parts by mass per 100 parts by mass of the (meth)acrylic compound (c-1). [7] The dental filling and restoring material according to any one of the above [1] to [6], wherein the mass of the organic fluorinating agent (A) is 0.1 to 10 parts by mass per 100 parts by mass of the total mass of the polymerizable monomer (C). [8] The dental filling and restoring material according to any one of the above [1] to [7], wherein the mass of the organic fluorinating agent (A) is 0.001 to 10 parts by mass per 100 parts by mass of the ion-releasing glass (B). [9] The dental filling and restoring material according to any one of the above [1] to [8], wherein the organic fluorinating agent (A) is an electrophilic fluorinating agent (A-2).
[10] The dental filling and restoring material according to any one of the above [1] to [9], wherein the organic fluorinating agent (A) is a compound containing a quaternary ammonium ion.
[11] The dental filling and restoring material according to any one of the above [1] to [9], wherein the organic fluorinating agent (A) is a hypervalent iodine compound.
[12] The dental filling and restoring material according to any one of the above [1] to
[11] , wherein the ion-releasing glass (B) is at least one type of glass selected from the group consisting of soda-lime silicate glass, aluminosilicate glass, borosilicate glass, aluminoborosilicate glass, and fluoroaluminoborosilicate glass.
[13] The dental filling and restoring material according to any one of the above [1] to
[12] , further comprising a peroxide (D).
[14] A dental filling and restoring material according to any one of the above [1] to
[13] , comprising a first material containing a peroxide (D) and a second material not containing a peroxide (D).
[15] The dental filling and restorative material according to
[14] above, wherein the second material comprises an organic fluorinating agent (A).
[16] A kit comprising the dental filling and restorative material according to any one of the above [1] to
[15] and a tooth surface treatment material.
[17] A kit comprising the dental filling and restoring material according to any one of the above [1] to
[15] and a dental adhesive. Effect of the Invention
[0006] INDUSTRIAL APPLICABILITY The present invention provides a dental filling and restorative material which has a high ability to strengthen tooth structure and can give a cured product which is excellent in strength and aesthetics. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0007] Hereinafter, the present invention will be described in detail with reference to embodiments. In this specification, the upper and lower limit values of the numerical ranges (contents of each component, values calculated from each component, and each physical property, etc.) can be appropriately combined. In addition, in this specification, the numerical values of each symbol in the formula can also be appropriately combined. In other words, in this specification, the lower limit and upper limit described in stages for numerical ranges can be combined independently. For example, the description of "preferably 10 to 90, more preferably 30 to 60" for the same item can be combined with the "preferable lower limit (10)" and the "more preferable upper limit (60)" to form "10 to 60." Furthermore, with regard to a numerical range, for example, based on the description of "preferably 10 to 90, more preferably 30 to 60," the upper limit value can be not particularly specified and only the lower limit value can be specified as "10 or more" or "30 or more," and similarly, the lower limit value can be not particularly specified and only the upper limit value can be specified as "90 or less" or "60 or less." Unless otherwise specified, when a numerical range is simply stated as "10 to 90", it indicates a range of 10 or more and 90 or less. As above, for example, from the description of "preferably 10 or more, more preferably 30 or more" and the description of "preferably 90 or less, more preferably 60 or less" for the same item, the "preferable lower limit (10)" and the "more preferable upper limit (60)" can be combined to form "10 or more and 60 or less." Also, as above, only the lower limit can be specified as "10 or more" or "30 or more," and similarly, only the lower limit can be specified as "90 or less" or "60 or less."
[0008] In this specification, the term "(meth)acrylic" is used to mean both "methacrylic" and "acrylic". The same applies to similar terms such as "(meth)acrylate", "(meth)acrylic acid ester", "(meth)acrylamide", and "(meth)acryloyloxy". In addition, in this specification, the term "(meth)acrylic monomer" or "(meth)acrylic compound" is used to mean both "(meth)acrylic acid ester compound" and "(meth)acrylamide and its derivatives." In this specification, the term "polymerizable monomer" is used to mean a monomer that can be polymerized by a polymerization initiator described below.
[0009] In addition, in this specification, unless otherwise specified, the expression "ion releasing" refers to the "fluoride ion releasing" of the cured product of the dental filling and restorative material which is one embodiment of the present invention. In addition, in this specification, unless otherwise specified, the terms "mechanical strength" and "strength" refer to the "flexural strength" and "flexural modulus" of the cured product of a dental filling and restorative material which is one embodiment of the present invention. In addition, in this specification, unless otherwise specified, the term "aesthetics" refers to the "aesthetics" of the cured product of the dental filling and restorative material which is one embodiment of the present invention. In addition, in this specification, unless otherwise specified, the expression "tooth substance strengthening ability" refers to the "tooth substance strengthening ability" of the hardened product of the dental filling and restorative material which is one embodiment of the present invention.
[0010] [Dental filling and restorative materials] A dental filling and restorative material according to an embodiment of the present invention contains an organic fluorinating agent (A), an ion-releasing glass (B), and a polymerizable monomer (C). The dental filling and restorative material has a high ability to strengthen tooth structure when hardened, and is also excellent in strength and aesthetics. In general, organic fluorinating agents (A) are components used to introduce fluorine into organic substances. The inventors have found that organic fluorinating agents (A) are also useful for inorganic tooth substances, and that dental filling and restorative materials containing organic fluorinating agents (A) can impart high tooth substance strengthening ability to their hardened products even if the amount of fluoride released is relatively low. This eliminates the need to increase the amount of organic fluorinating agents (A), and as a result, high tooth substance strengthening ability can be obtained without impairing strength or aesthetics. The reason why the tooth structure strengthening ability is improved by blending an organic fluorinating agent (A) with a dental filling and restorative material is, but not limited to, that the cations contained in the organic fluorinating agent promote the incorporation of fluorine atoms into the tooth structure (in other words, OH - and F - It is speculated that one of the reasons for this is that the government is promoting the exchange of information between companies. More specifically, it is speculated as follows. For example, when a fluorinating agent XF fluorinates an organic compound R-OH, it may take the form of ROX and then RF. A similar phenomenon occurs in hydroxyapatite Ca 10 It is possible that fluorination also occurs in (PO4)6(OH)2, and that by passing through the Ca-OX form, it becomes easier to form Ca-F bonds, making it easier to convert to fluoroapatite or CaF2. It is also known that the efficiency of fluorination of certain fluorinating agents increases when they coexist with CaF2, which is not a fluorinating agent in its own right. It is possible that the conversion of hydroxyapatite to CaF2 accelerates further fluorination, i.e., the formation of Ca-F bonds.
[0011] Furthermore, the inventors have found through their investigations that the coexistence of the ion-releasing glass (B) and the organic fluorinating agent (A) gives the hardened product not only high tooth structure strengthening ability, but also strength and aesthetic properties. The ion-releasing glass (B) is a glass in which free ions are weakly chelated to a strong glass skeleton, and the strength can be maintained by the glass skeleton even after the release of the free ions. However, as mentioned above, in order to ensure the fluidity required for use as a dental filling and restorative material, there is an upper limit to the amount of ion-releasing glass (B) that can be blended. For this reason, it is difficult to sufficiently improve the ion-releasing property and the tooth structure strengthening ability resulting from it by using the ion-releasing glass (B) alone. In the dental filling and restoring material according to the embodiment of the present invention, by making the ion-releasing glass (B) and the organic fluorinating agent (A) coexist, the hardened material of the dental filling and restoring material can have high tooth substance strengthening ability, strength, and aesthetics without excessively increasing the amount of both components in the dental filling and restoring material. This is presumably due to the combined action of (i) the above-mentioned effect of improving the tooth substance strengthening ability due to the promotion of the incorporation of fluorine atoms into the tooth substance by the cations contained in the organic fluorinating agent (A) and the strength ensured by the glass skeleton of the ion-releasing glass (B), (ii) the effect of the cations contained in the ion-releasing glass (B) and the organic fluorinating agent (A) forming an insoluble salt on the tooth substance surface, which makes the tooth substance more likely to be protected from acid, and (iii) the above-mentioned effect of promoting fluorination due to the coexistence with CaF2.
[0012] The dental filling and restoring material may be a one-material type or a two-material type. In the case of the two-material type, it is preferable to pack a specific plurality of components separately into the first material and the second material in order to enhance storage stability, as described later.
[0013] From the viewpoint of easily improving the strength and color tone of the obtained cured product, the dental filling and restoring material preferably has a small solvent content, and is preferably (i) an embodiment that does not contain a solvent, or (ii) an embodiment that further contains a solvent, and the mass of the solvent is preferably more than 0 mass part and 1.0 mass part or less with respect to the total mass 100 mass parts of the dental filling and restoring material. The content of the solvent is more preferably 0.5 mass parts or less, even more preferably 0.1 mass parts or less, and even more preferably 0.05 mass parts or less. Examples of the solvent include water, ethanol, and acetone.
[0014] The total mass of the organic fluorinating agent (A), the ion-releasing glass (B), and the polymerizable monomer (C) in the dental filling and restoring material is preferably 90% by mass or more, more preferably 95% by mass or more, even more preferably 98% by mass or more, and even more preferably 99% by mass or more, or may be 100% by mass, from the viewpoint of ensuring the desired tooth substance strengthening ability, aesthetics, and strength of the cured product. In other words, the total mass of the organic fluorinating agent (A), the ion-releasing glass (B), and the polymerizable monomer (C) in the dental filling and restoring material is preferably 90 to 100% by mass.
[0015] <Organic fluorinating agent (A)> The organic fluorinating agent (A) contained in the dental filling and restoring material is a fluorinating agent containing at least one carbon atom and at least one fluorine atom in the molecule. The organic fluorinating agent (A) contains highly reactive fluorine atoms, and thus improves the tooth substance strengthening ability while maintaining an appropriate ion release property in the dental filling and restoring material. The organic fluorinating agent (A) is roughly classified into nucleophilic fluorinating agent (A-1) in which fluorine anion acts as a reactive species, and electrophilic fluorinating agent (A-2) in which electron-deficient fluorine atom acts as a reactive species. In the above dental filling and restorative material, any organic fluorinating agent can be used, and nucleophilic fluorinating agent (A-1) is preferred in terms of excellent solubility and ease of blending, while electrophilic fluorinating agent (A-2) is preferred in terms of realizing high improvement of tooth substance strengthening ability even with a small amount.
[0016] In both the nucleophilic fluorinating agent (A-1) and the electrophilic fluorinating agent (A-2), the organic fluorinating agent (A) preferably contains at least one element selected from the group consisting of nitrogen, phosphorus, boron, sulfur, and iodine as an element other than carbon and fluorine from the viewpoint of improving bactericidal activity. In the case of the electrophilic fluorinating agent (A-2), it is more preferable to contain at least one element selected from the group consisting of nitrogen, boron, and iodine. In the case of the nucleophilic fluorinating agent (A-1), it is more preferable to contain at least one element selected from the group consisting of nitrogen and sulfur.
[0017] From the viewpoint of improving the bactericidal activity, the organic fluorinating agent (A), whether a nucleophilic fluorinating agent (A-1) or an electrophilic fluorinating agent (A-2), is preferably a compound containing a quaternary ammonium ion.
[0018] In addition, from the viewpoint of improving the bactericidal activity, the organic fluorinating agent (A), whether it is a nucleophilic fluorinating agent (A-1) or an electrophilic fluorinating agent (A-2), is preferably a hypervalent iodine compound.
[0019] The molecular weight of the organic fluorinating agent (A) is preferably 100 to 500, more preferably 150 to 400, and even more preferably 200 to 300, from the viewpoints of solubility and storage stability.
[0020] (Nucleophilic Fluorinating Agent (A-1)) From the viewpoints of solubility and ease of incorporation, the organic fluorinating agent (A) is preferably a nucleophilic fluorinating agent (A-1). The nucleophilic fluorinating agent (A-1) may be any compound in which a fluorine anion acts as a reactive species, and examples thereof include at least one compound selected from the group consisting of the following compounds: Tetramethylammonium fluoride; tetraethylammonium fluoride; tetrabutylammonium fluoride (abbreviation: TBAF); tetrabutylammonium difluorotriphenylsilicate; tetrabutylammonium difluorotriphenyltin; tetrabutylammonium bifluoride; and tetraalkylammonium compounds, which are compounds containing quaternary ammonium ions, such as tetrabutylammonium dihydrogen trifluoride; Sulfur trifluoride compounds such as morpholinosulfur trifluoride (abbreviation: Morph-DAST); bis(2-methoxyethyl)aminosulfur trifluoride; 4-tert-butyl-2,6-dimethylphenylsulfur trifluoride; (diethylamino)sulfur trifluoride; and sulfur trifluoride diethylamine complex; Perfluoro-1-butanesulfonyl fluoride; and sulfonyl fluoride salts such as pyridine-2-sulfonyl fluoride; Fluoroalkylamine compounds such as hexafluoropropene diethylamine; Pyridinium compounds such as 2-fluoro-1-methylpyridinium p-toluenesulfonate; Imidazolium compounds such as 1,3-bis(2,6-diisopropylphenyl)-2-fluoroimidazolium tetrafluoroborate; and 2-chloro-1,3-bis(2,6-diisopropylphenyl)-1H-imidazolium chloride-cesium fluoride; Pyrimidine-2-sulfonyl fluoride; pyrimidin(-one) compounds such as tetrahydro-1,3-dimethyl-2(1H)-pyrimidinone hydrofluoride; and Hypervalent iodine compounds such as pyridinium pentafluoroiodide-hydrogen fluoride complex; hydrate salts thereof; and These hydrofluoric acid salts.
[0021] Among them, from the viewpoint of safety to living organisms, tetraalkylammonium compounds containing quaternary ammonium salts, sulfonyl fluoride salts, fluoroalkylamine compounds, pyridinium compounds, imidazolium compounds, and hypervalent iodine compounds are preferred, from the viewpoint of stability in air, tetraalkylammonium compounds containing quaternary ammonium salts, fluoroalkylamine compounds, pyridinium compounds, imidazolium compounds, and hypervalent iodine compounds are more preferred, and from the viewpoint of excellent water solubility and tooth substance strengthening ability, tetraalkylammonium compounds containing quaternary ammonium salts, fluoroalkylamine compounds, pyridinium compounds, and hypervalent iodine compounds are even more preferred.Furthermore, from the viewpoint of being able to impart bactericidal properties and making caries prevention more effective, tetraalkylammonium compounds containing quaternary ammonium salts, pyridinium compounds, and hypervalent iodine compounds are preferred.
[0022] (Electrophilic Fluorinating Agent (A-2)) From the viewpoint of easily realizing a high degree of improvement in tooth structure strengthening ability with a small amount, the organic fluorinating agent (A) is preferably an electrophilic fluorinating agent (A-2).
[0023] The electrophilic fluorinating agent (A-2) may be any compound in which an electron-deficient fluorine atom acts as a reactive species, and examples thereof include at least one compound selected from the group consisting of the following compounds: Cyclic ammonium compounds including quaternary ammonium salts such as N-fluoro-N'-(chloromethyl)triethylenediaminebis(tetrafluoroborate) (abbreviation: F-TEDA-BF4); Pyridinium compounds such as 1-fluoropyridinium trifluoromethanesulfonate (abbreviation: FPTS); 1,1'-difluoro-2,2'-bipyridinium bis(tetrafluoroborate); 1-fluoro-2,4,6-trimethylpyridinium tetrafluoroborate (abbreviation: FTP-BF4); Sulfonimide compounds such as N-fluorobenzenesulfonimide; and Hypervalent iodine compounds such as 1-fluoro-3,3-dimethyl-1,2-benzoiodoxole (abbreviation: FDBI); hydrate salts thereof; and These hydrofluoric acid salts.
[0024] Among them, cyclic ammonium compounds, pyridinium compounds, sulfonimide compounds, and hypervalent iodine compounds are preferred from the viewpoints of safety to living organisms, stability in air, and excellent tooth strengthening ability even at low concentrations.Furthermore, cyclic ammonium compounds containing quaternary ammonium salts, pyridinium compounds, and hypervalent iodine compounds are preferred from the viewpoints of being able to impart bactericidal properties and making caries prevention more effective.
[0025] The organic fluorinating agent (A) has a high tooth structure strengthening ability and is used from the viewpoint of easily obtaining a hardened product excellent in strength and aesthetics. The organic fluorinating agent (A-1) is a nucleophilic fluorinating agent, such as tetramethylammonium fluoride, tetraethylammonium fluoride, tetrabutylammonium fluoride, tetrabutylammonium difluorotriphenyltin, tetrabutylammonium difluorotriphenylsilicate, pyrimidine-2-sulfonyl fluoride, pyridine-2-sulfonyl fluoride, 2-chloro-1,3-bis(2,6-diisopropylphenyl)-1H-imidazolium chloride-cesium fluoride, perfluoro-1-butanesulfonyl fluoride, morpholinosulfur trifluoride, hexafluoropropene diethylamine, 2-fluoro-1-methylpyridinium p-toluenesulfonate; (diethylamino)sulfur trifluoride; 4-tert-butyl-2,6-dimethylphenylsulfur trifluoride; bis(2-methoxyethyl)aminosulfur trifluoride; 1,3-bis(2,6-diisopropylphenyl)-2-fluoroimidazolium tetrafluoroborate; and salts thereof, and the electrophilic fluorinating agent (A-2) is at least one compound selected from the group consisting of 1-fluoropyridinium trifluoromethanesulfonate; 1,1'-difluoro-2,2'-bipyridinium bis(tetrafluoroborate); 1-fluoro-2,4,6-trimethylpyridinium tetrafluoroborate; 1-fluoro-3,3-dimethyl-1,2-benzoiodoxol; N-fluoro-N'-(chloromethyl)triethylenediamine bis(tetrafluoroborate); N-fluorobenzenesulfonimide; and salts thereof.
[0026] (Mass of organic fluorinating agent (A) in dental filling and restorative materials) As described above, the hardened dental filling and restorative material containing the organic fluorinating agent (A) exhibits excellent tooth structure strengthening ability even at a relatively low fluoride release amount. Therefore, the amount of the organic fluorinating agent (A) used in the dental filling and restorative material can be relatively small, and as a result, the hardened dental filling and restorative material has high tooth structure strengthening ability while suppressing deterioration in aesthetics and strength.
[0027] The mass of the organic fluorinating agent (A) in the dental filling and restoring material is preferably 0.1 to 10 parts by mass, more preferably 0.2 to 5 parts by mass, and even more preferably 0.5 to 2.5 parts by mass, relative to 100 parts by mass of the total mass of the polymerizable monomer (C) in the dental filling and restoring material. By making the mass of the organic fluorinating agent (A) 0.1 parts by mass or more, it is possible to obtain an excellent tooth substance strengthening ability. By making the mass of the organic fluorinating agent (A) 10 parts by mass or less, it is possible to suppress changes in physical properties due to water absorption and dissolution of fluorine.
[0028] The mass of the organic fluorinating agent (A) in the dental filling and restoring material is preferably 0.001 to 10 parts by mass, more preferably 0.01 to 7 parts by mass, and even more preferably 0.05 to 3 parts by mass, relative to 100 parts by mass of the ion-releasing glass (B). If the mass is 0.001 parts by mass or more, the tooth substance strengthening ability of the hardened material of the dental filling and restoring material is easily improved. If the mass is 10 parts by mass or less, the aesthetics and strength of the hardened material of the dental filling and restoring material are easily ensured.
[0029] In addition, the mass of the organic fluorinating agent (A) in the dental filling and restorative material is preferably 0.005 to 30 parts by mass, more preferably 0.01 to 20 parts by mass, and even more preferably 0.1 to 10 parts by mass, relative to 100 parts by mass of the (meth)acrylic compound (c-1) described later, from the viewpoint of easily ensuring good tooth substance strengthening ability and solubility.
[0030] When the dental filling and restoring material is a two-material type, the mass of the organic fluorinating agent (A) in the dental filling and restoring material means the total mass of the organic fluorinating agent (A) contained in the first material and the organic fluorinating agent (A) contained in the second material. In this case, the mass of the component that is the basis for the content of the organic fluorinating agent (A) is also the total mass of the mass of the component contained in the first material and the mass of the component contained in the second material. The same applies to the contents of other components described below.
[0031] The content of the organic fluorinating agent (A) in the dental filling and restoring material is preferably 0.005 to 5 mass%, more preferably 0.008 to 4 mass%, even more preferably 0.01 to 3.5 mass%, and even more preferably 0.01 to 3 mass%, relative to the total mass of the dental filling and restoring material, from the viewpoint of easily ensuring ion release properties and tooth structure strengthening ability.
[0032] <Ion-releasing glass (B)> The ion-releasing glass (B) performs fluoride-releasing and recharging, thereby improving the ion-releasing property and tooth substance strengthening ability of the hardened product of the dental filling and restorative material. The ion-releasing glass (B) can be any glass without any limitations, so long as it contains one or more network-forming elements that form the glass skeleton and one or more network-modifying elements that modify the glass skeleton. Specific examples of the network skeleton-forming elements contained in the ion-releasing glass (B) include silicon, oxygen, aluminum, boron, phosphorus, germanium, vanadium, etc. These network skeleton-forming elements may be used alone or in combination. Specific examples of the network modifier element include halogen elements such as fluorine, bromine, and iodine, alkali metal elements such as sodium and lithium, alkaline earth metal elements such as calcium and strontium, Group 3 elements such as scandium, yttrium, and lanthanum, tin, gallium, indium, thorium, barium, cesium, and rubidium. These elements can be used alone or in combination. Furthermore, the ion-releasing glass (B) may contain an intermediate element which replaces a part of the network-forming element to participate in network formation and also plays a role as a network-modifying element. Specific examples of the intermediate element include titanium, zinc, lead, beryllium, zirconium, etc., and these elements may be used alone or in combination. From the viewpoint of ion-releasing ability, the ion-releasing glass (B) is preferably at least one glass selected from the group consisting of soda-lime silicate glass, aluminosilicate glass, borosilicate glass, aluminoborosilicate glass, and fluoroaluminoborosilicate glass. Examples of the aluminosilicate glass include fluorine-containing glasses such as fluoroaluminosilicate glass, fluoroborosilicate glass, calcium fluoroaluminosilicate glass, strontium fluoroaluminosilicate glass, barium fluoroaluminosilicate glass, and strontium calcium fluoroaluminosilicate glass.
[0033] The method for producing the ion-releasing glass (B) is not particularly limited, and the glass can be produced by a melting method, a sol-gel method, etc. Among these, the method for producing the glass by a melting method using a melting furnace is preferred from the viewpoint of ease of designing the glass composition including the selection of raw materials. Although the ion-releasing glass (B) has an amorphous structure, there is no problem if it contains a part of a crystalline structure, and there is no problem if it is a mixture of a glass having an amorphous structure and a glass having a crystalline structure. Whether the glass structure is amorphous or not can be determined using analytical equipment such as X-ray diffraction analysis or a transmission electron microscope. Among them, the ion-releasing glass (B) used in the dental filling and restorative material according to the embodiment of the present invention is preferably an amorphous structure, which is a homogeneous structure, since fluoride ions are gradually released due to an equilibrium relationship with the ion concentration in the external environment.
[0034] The ion-releasing glass (B) may be used alone, or may be made fine by pulverization, or may be made coarse by physical treatment such as compression or chemical treatment using a binder, so as to adjust the particle size and particle size distribution.
[0035] The ion-releasing glass (B) may be used as it is, or may be surface-treated. Specific examples of the surface treatment agent used for the surface treatment include surfactants, fatty acids, organic acids, inorganic acids, monomers, polymers, various coupling agents, silane compounds, metal alkoxide compounds, and partial condensates thereof.
[0036] From the viewpoints of ion-releasing property and bending strength, the mass of the ion-releasing glass (B) in the dental filling and restoring material is preferably 25 to 85 parts by mass, more preferably 40 to 80 parts by mass, and even more preferably 50 to 80 parts by mass, relative to 100 parts by mass of the total mass of the dental filling and restoring material.
[0037] <Polymerizable monomer (C)> As the polymerizable monomer (C), a radical polymerizable monomer is preferably used. Specific examples of the radical polymerizable monomer include (meth)acrylate polymerizable monomers; (meth)acrylamide polymerizable monomers; esters of α-cyanoacrylic acid, α-halogenated acrylic acid, crotonic acid, cinnamic acid, sorbic acid, maleic acid, itaconic acid, etc.; vinyl esters; vinyl ethers; mono-N-vinyl derivatives; styrene derivatives, etc. As the polymerizable monomer (C), from the viewpoint of curability, (meth)acrylate polymerizable monomers and (meth)acrylamide polymerizable monomers are preferred.
[0038] Examples of the polymerizable monomer (C) include a monofunctional polymerizable monomer having one polymerizable group and a polyfunctional polymerizable monomer having multiple polymerizable groups. From the viewpoint of excellent curability, it is preferable that a polyfunctional polymerizable monomer is contained. From the viewpoint of excellent flexibility and improving the toughness of the cured product, it is preferable that a monofunctional polymerizable monomer is contained.
[0039] The monofunctional polymerizable monomer can be any compound having one polymerizable group in one molecule without any limitations. Specific examples include monofunctional polymerizable monomers containing any of a hydroxyl group, an acidic group, an amino group, an amide group, and a urethane bond; and monofunctional polymerizable monomers containing none of a hydroxyl group, an acidic group, an amino group, an amide group, and a urethane bond.
[0040] Examples of the monofunctional polymerizable monomer having a hydroxyl group in one molecule include hydroxy(meth)acrylate compounds such as 2-hydroxyethyl(meth)acrylate, 2-hydroxypropyl(meth)acrylate, 2-hydroxybutyl(meth)acrylate, 6-hydroxyhexyl(meth)acrylate, 10-hydroxydecyl(meth)acrylate, 3-chloro-2-hydroxypropyl(meth)acrylate, 2-hydroxy-3-phenoxypropyl(meth)acrylate, glycerin mono(meth)acrylate, and 2-hydroxy-3-acryloyloxypropyl(meth)acrylate. These may be used alone or in combination of two or more. In the dental filling and restoring material, these impart adhesiveness to the dental filling and restoring material and impart ion releasing properties to the hardened product of the dental filling and restoring material.
[0041] Examples of monofunctional polymerizable monomers having an acidic group in one molecule include polymerizable monomers having at least one acidic group such as a phosphoric acid group, a pyrophosphoric acid group, a thiophosphoric acid group, a phosphonic acid group, a sulfonic acid group, a carboxylic acid group, etc., and at least one polymerizable group such as an acryloyl group, a methacryloyl group, a vinyl group, a styrene group, etc. The acidic group-containing polymerizable monomer has affinity for the adherend and has a demineralizing effect on the tooth structure.
[0042] Examples of the phosphoric acid group-containing polymerizable monomer include 2-(meth)acryloyloxyethyl dihydrogen phosphate; 3-(meth)acryloyloxypropyl dihydrogen phosphate; 4-(meth)acryloyloxybutyl dihydrogen phosphate; 5-(meth)acryloyloxypentyl dihydrogen phosphate; 6-(meth)acryloyloxyhexyl dihydrogen phosphate; 7-(meth)acryloyloxyheptyl dihydrogen phosphate; 8-(meth)acryloyloxyoctyldihydrogenphosphate;9-(meth)acryloyloxynonyldihydrogenphosphate;10-(meth)acryloyloxydecyldihydrogenphosphate;11-(meth)acryloyloxyundecyldihydrogenphosphate;12-(meth)acryloyloxydodecyldihydrogenphosphate;16-(meth)acryloyloxyhexadecyldihydrogenphosphate;20-(meth)acryloyloxyoctyldihydrogenphosphate HYDROGEN PHOSPHATE;Bis[2-(meth)acryloyloxyethyl]hydrogen phosphate;Bis[4-(meth)acryloyloxybutyl]hydrogen phosphate;Bis[6-(meth)acryloyloxyhexyl]hydrogen phosphate;Bis[8-(meth)acryloyloxyoctyl]hydrogen phosphate;Bis[9-(meth)acryloyloxynonyl]hydrogen phosphate;Bis[10-(meth)acryloyloxy 2-(meth)acryloyloxyethyl-2-bromoethyl hydrogen phosphate; bis[2-(meth)acryloyloxy-(1-hydroxymethyl)ethyl]hydrogen phosphate; acid chlorides thereof; alkali metal salts thereof; and ammonium salts thereof.
[0043] Examples of the pyrophosphate group-containing polymerizable monomer include bis[2-(meth)acryloyloxyethyl]pyrophosphate; bis[4-(meth)acryloyloxybutyl]pyrophosphate; bis[6-(meth)acryloyloxyhexyl]pyrophosphate; bis[8-(meth)acryloyloxyoctyl]pyrophosphate; bis[10-(meth)acryloyloxydecyl]pyrophosphate; acid chlorides thereof; alkali metal salts thereof; and ammonium salts thereof.
[0044] Examples of the thiophosphate group-containing polymerizable monomer include 2-(meth)acryloyloxyethyl dihydrogen thiophosphate; 3-(meth)acryloyloxypropyl dihydrogen thiophosphate; 4-(meth)acryloyloxybutyl dihydrogen thiophosphate; 5-(meth)acryloyloxypentyl dihydrogen thiophosphate; 6-(meth)acryloyloxyhexyl dihydrogen thiophosphate; 7-(meth)acryloyloxyheptyl dihydrogen thiophosphate; 8-(meth)acryloyloxyoctyl dihydrogen thiophosphate. acryloyloxynonyl dihydrogen thiophosphate; 10-(meth)acryloyloxydecyl dihydrogen thiophosphate; 11-(meth)acryloyloxyundecyl dihydrogen thiophosphate; 12-(meth)acryloyloxydodecyl dihydrogen thiophosphate; 16-(meth)acryloyloxyhexadecyl dihydrogen thiophosphate; 20-(meth)acryloyloxyeicosyl dihydrogen thiophosphate; acid chlorides thereof; alkali metal salts thereof; and ammonium salts thereof.
[0045] Examples of the phosphonic acid group-containing polymerizable monomer include 2-(meth)acryloyloxyethyl phenyl phosphonate; 5-(meth)acryloyloxypentyl-3-phosphonopropionate; 6-(meth)acryloyloxyhexyl-3-phosphonopropionate; 10-(meth)acryloyloxydecyl-3-phosphonopropionate; 6-(meth)acryloyloxyhexyl-3-phosphonoacetate; 10-(meth)acryloyloxydecyl-3-phosphonoacetate; acid chlorides thereof; alkali metal salts thereof; and ammonium salts thereof.
[0046] Examples of the sulfonic acid group-containing polymerizable monomer include 2-(meth)acrylamide-2-methylpropanesulfonic acid; styrenesulfonic acid; and 2-sulfoethyl(meth)acrylate.
[0047] Carboxylic acid group-containing polymerizable monomers include, for example, polymerizable monomers having one carboxyl group in the molecule and polymerizable monomers having multiple carboxyl groups in the molecule.
[0048] Examples of polymerizable monomers having one carboxyl group in the molecule include (meth)acrylic acid; N-(meth)acryloylglycine; N-(meth)acryloylaspartic acid; O-(meth)acryloyltyrosine; N-(meth)acryloyltyrosine; N-(meth)acryloylphenylalanine; N-(meth)acryloyl-p-aminobenzoic acid; N-(meth)acryloyl-o-aminobenzoic acid; p-vinylbenzoic acid; 2-(meth)acryloyloxy Benzoic acid; 3-(meth)acryloyloxybenzoic acid; 4-(meth)acryloyloxybenzoic acid; N-(meth)acryloyl-5-aminosalicylic acid; N-(meth)acryloyl-4-aminosalicylic acid; 2-(meth)acryloyloxyethyl hydrogen succinate; 2-(meth)acryloyloxyethyl hydrogen phthalate; 2-(meth)acryloyloxyethyl hydrogen malate; and acid halides thereof.
[0049] Examples of polymerizable monomers having multiple carboxyl groups in the molecule include 6-(meth)acryloyloxyhexane-1,1-dicarboxylic acid; 9-(meth)acryloyloxynonane-1,1-dicarboxylic acid; 10-(meth)acryloyloxydecane-1,1-dicarboxylic acid; 11-(meth)acryloyloxyundecane-1,1-dicarboxylic acid; 12-(meth)acryloyloxydodecane-1,1-dicarboxylic acid; 13-(meth)acryloyloxytridecane-1,1-dicarboxylic acid; 4-(meth)acryloyloxyhexane-1,1-dicarboxylic acid; Examples of the acid anhydride include 4-(meth)acryloyloxyethyl trimellitate; 4-(meth)acryloyloxyethyl trimellitate anhydride; 4-(meth)acryloyloxybutyl trimellitate; 4-(meth)acryloyloxyhexyl trimellitate; 4-(meth)acryloyloxydecyl trimellitate; 2-(meth)acryloyloxyethyl-3'-(meth)acryloyloxy-2'-(3,4-dicarboxybenzoyloxy)propyl succinate; acid anhydrides thereof; and acid halides thereof.
[0050] The above-mentioned acidic group-containing polymerizable monomer may be used alone or in combination of two or more. Among these acidic group-containing polymerizable monomers, from the viewpoint of high adhesive strength to dental adherends, one or more selected from the group consisting of phosphoric acid group-containing polymerizable monomers, carboxylic acid group-containing polymerizable monomers, and sulfonic acid group-containing polymerizable monomers are preferred, and one or more selected from the group consisting of phosphoric acid group-containing polymerizable monomers having two or more hydroxyl groups bonded to phosphorus atoms, polymerizable monomers having multiple carboxyl groups in the molecule, and sulfonic acid group-containing polymerizable monomers are more preferred, and 10-(meth)acryloyloxydecyl dihydride is more preferred. More preferred is one or more selected from the group consisting of acryloyloxypropyl dihydrogen phosphate, 1,3-di(meth)acryloyloxypropyl dihydrogen phosphate, 2-(meth)acryloyloxyethyl dihydrogen phosphate, 4-(meth)acryloyloxyethyl trimellitate anhydride, 4-(meth)acryloyloxyethyl trimellitate, 2-(meth)acrylamido-2-methylpropanesulfonic acid, and 11-(meth)acryloyloxyundecane-1,1-dicarboxylic acid.
[0051] The mass of the acidic group-containing polymerizable monomer in the dental filling and restoring material is preferably 1 to 50 parts by mass, more preferably 2 to 30 parts by mass, and even more preferably 2 to 15 parts by mass, relative to 100 parts by mass of the total mass of the polymerizable monomer (C) in the dental filling and restoring material. When the mass of the acidic group-containing polymerizable monomer is 1 part by mass or more, it is easy to obtain high adhesion to various dental adherends, and when the mass of the acidic group-containing polymerizable monomer is 50 parts by mass or less, it is easy to maintain a balance between polymerizability and adhesion.
[0052] Examples of monofunctional polymerizable monomers having an amino group in one molecule include aminoethyl (meth)acrylate; 2-dimethylaminoethyl (meth)acrylate; 2-diethylaminoethyl (meth)acrylate; 2-dipropylaminoethyl (meth)acrylate; 2-diisopropylaminoethyl (meth)acrylate; and 2-dibutylaminoethyl (meth)acrylate. Examples of monofunctional polymerizable monomers having an amide group in one molecule include (meth)acrylamide; N-(meth)acryloylmorpholine; N,N-dimethyl(meth)acrylamide; N,N-diethyl(meth)acrylamide; N,N-di-n-propyl(meth)acrylamide; N,N-di-n-butyl(meth)acrylamide; N,N-di-n-hexyl(meth)acrylamide; N,N-di-n-octyl(meth)acrylamide; N,N-di-2-ethylhexyl(meth)acrylamide. Examples of suitable acrylamides include N-hydroxyethyl(meth)acrylamide; N,N-bis(2-hydroxyethyl)acrylamide; N-(meth)acryloylcarbazole; N-methyl-N-phenyl(meth)acrylamide; N-(meth)acryloylmorpholine; N-piperidinyl acrylamide; N-tetramethylpiperidinyl acrylamide; N-2-methylpiperidinyl acrylamide; N-3-methylpiperidinyl acrylamide; and N-4-methylpiperidinyl acrylamide.
[0053] Examples of monofunctional polymerizable monomers not containing any of a hydroxyl group, an acidic group, an amino group, an amide group, and a urethane bond in one molecule include, for example, o-phenylphenol(meth)acrylate; m-phenylphenol(meth)acrylate; p-phenylphenol(meth)acrylate; methoxylated-o-phenylphenol(meth)acrylate; methoxylated-m-phenylphenol(meth)acrylate; methoxylated-p-phenylphenol(meth)acrylate; ethoxylated-o-phenylphenol(meth)acrylate; ethoxylated-m -Phenylphenol (meth)acrylate;Ethoxylated-p-phenylphenol (meth)acrylate;Propoxylated-o-phenylphenol (meth)acrylate;Propoxylated-m-phenylphenol (meth)acrylate;Propoxylated-p-phenylphenol (meth)acrylate;Butoxylated-o-phenylphenol (meth)acrylate;Butoxylated-m-phenylphenol (meth)acrylate;Butoxylated-p-phenylphenol (meth)acrylate;o-Phenoxybenzyl (meth)acrylate;m-Phenoxy 2-(o-phenoxyphenyl)ethyl (meth)acrylate;2-(m-phenoxyphenyl)ethyl (meth)acrylate;2-(p-phenoxyphenyl)ethyl (meth)acrylate;3-(o-phenoxyphenyl)propyl (meth)acrylate;3-(m-phenoxyphenyl)propyl (meth)acrylate;3-(p-phenoxyphenyl)propyl (meth)acrylate;4-(o-phenoxyphenyl)butyl (meth)acrylate;4-(m -phenoxyphenyl)butyl (meth)acrylate;4-(p-phenoxyphenyl)butyl (meth)acrylate;5-(o-phenoxyphenyl)pentyl (meth)acrylate;5-(m-phenoxyphenyl)pentyl (meth)acrylate;5-(p-phenoxyphenyl)pentyl (meth)acrylate;6-(o-phenoxyphenyl)hexyl (meth)acrylate;6-(m-phenoxyphenyl)hexyl (meth)acrylate;6-(p-phenoxyphenyl)hexyl (meth)acrylate;Methyl (meth)acrylate;Examples of the acrylates include ethyl (meth)acrylate, propyl (meth)acrylate, isopropyl (meth)acrylate, n-butyl (meth)acrylate, sec-butyl (meth)acrylate, t-butyl (meth)acrylate, isobutyl (meth)acrylate, n-hexyl (meth)acrylate, cyclohexyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, lauryl (meth)acrylate, cetyl (meth)acrylate, stearyl (meth)acrylate, isobornyl (meth)acrylate, benzyl (meth)acrylate, phenyl (meth)acrylate, 2,3-dibromopropyl (meth)acrylate, 3-(meth)acryloyloxypropyltrimethoxysilane, and 11-(meth)acryloyloxyundecyltrimethoxysilane. These may be used alone or in combination of two or more. These can be suitably used in the dental filling and restoring material from the viewpoint of imparting effects of lowering the viscosity of the dental filling and restoring material, improving the strength of the cured product, and further improving the adhesive durability due to excellent water resistance.
[0054] Among these, in view of excellent strength and adhesive durability of the cured product of the dental filling and restorative material, ethoxylated-o-phenylphenol (meth)acrylate, ethoxylated-m-phenylphenol (meth)acrylate, ethoxylated-p-phenylphenol (meth)acrylate, propoxylated-o-phenylphenol (meth)acrylate, propoxylated-m-phenylphenol (meth)acrylate, propoxylated-p-phenylphenol (meth)acrylate, o-phenoxybenzyl (meth)acrylate, m-phenoxybenzyl (meth)acrylate, p-phenoxybenzyl (meth)acrylate, 2-(o-phenoxyphenyl)ethyl (meth)acrylate, 2-(m-phenoxyphenyl)ethyl (meth)acrylate are particularly preferred. , 2-(p-phenoxyphenyl)ethyl (meth)acrylate, and lauryl (meth)acrylate are preferred, with ethoxylated-o-phenylphenol (meth)acrylate, ethoxylated-m-phenylphenol (meth)acrylate, ethoxylated-p-phenylphenol (meth)acrylate, o-phenoxybenzyl (meth)acrylate, m-phenoxybenzyl (meth)acrylate, p-phenoxybenzyl (meth)acrylate, and lauryl (meth)acrylate being more preferred, with ethoxylated-o-phenylphenol (meth)acrylate, ethoxylated-m-phenylphenol (meth)acrylate, o-phenoxybenzyl (meth)acrylate, and m-phenoxybenzyl (meth)acrylate being even more preferred. Furthermore, in the preferred embodiments described above, it is even more preferable that each of them is a methacrylate type compound, and ethoxylated-o-phenylphenol methacrylate, ethoxylated-m-phenylphenol methacrylate, o-phenoxybenzyl methacrylate, and m-phenoxybenzyl methacrylate (abbreviation: POB-MA) are even more preferable.
[0055] The polyfunctional polymerizable monomer can be any compound having two or more polymerizable groups in one molecule, and specific examples thereof include polyfunctional polymerizable monomers containing any of a hydroxyl group, an acidic group, an amino group, an amide group, and a urethane bond; and polyfunctional polymerizable monomers containing none of a hydroxyl group, an acidic group, an amino group, an amide group, and a urethane bond.
[0056] Examples of polyfunctional polymerizable monomers having a hydroxyl group in one molecule include glycerol di(meth)acrylate; 1,2-bis(3-(meth)acryloyloxy-2-hydroxypropoxy)ethane; 2,2-bis[4-(3-(meth)acryloyloxy)-2-hydroxypropoxyphenyl]propane; and pentaerythritol tri(meth)acrylate. These may be used alone or in combination of two or more. Among these, from the viewpoint of excellent effect of improving the adhesion durability of the dental filling and restorative material and the ion release property of the cured product, glycerol di(meth)acrylate and 1,2-bis(3-(meth)acryloyloxy-2-hydroxypropoxy)ethane are preferred, and glycerol dimethacrylate and 1,2-bis(3-methacryloyloxy-2-hydroxypropoxy)ethane are more preferred.
[0057] Examples of polyfunctional polymerizable monomers having an acidic group in one molecule include bis[2-(meth)acryloyloxyethyl]hydrogen phosphate; bis[4-(meth)acryloyloxybutyl]hydrogen phosphate; bis[6-(meth)acryloyloxyhexyl]hydrogen phosphate; bis[8-(meth)acryloyloxyoctyl]hydrogen phosphate; bis[9-(meth)acryloyloxynonyl]hydrogen phosphate; bis[10- bis[(meth)acryloyloxydecyl]pyrophosphate; 1,3-di(meth)acryloyloxypropyl dihydrogen phosphate; bis[2-(meth)acryloyloxyethyl]pyrophosphate; bis[4-(meth)acryloyloxybutyl]pyrophosphate; bis[6-(meth)acryloyloxyhexyl]pyrophosphate; bis[8-(meth)acryloyloxyoctyl]pyrophosphate; and bis[10-(meth)acryloyloxydecyl]pyrophosphate.
[0058] An example of a polyfunctional polymerizable monomer having an amino group in one molecule is N,N-(2,2,4-trimethylhexamethylene)bis[2-(aminocarboxy)propane-1,3-diol]tetra(meth)acrylate.
[0059] Examples of polyfunctional polymerizable monomers having an amide group in one molecule include N-methacryloyloxyethyl acrylamide; N-methacryloyloxypropyl acrylamide; N-methacryloyloxybutyl acrylamide; N-(1-ethyl-(2-methacryloyloxy)ethyl)acrylamide; and N-(2-(2-methacryloyloxyethoxy)ethyl)acrylamide.
[0060] Examples of polyfunctional polymerizable monomers having a urethane bond in one molecule include urethane-modified (meth)acrylate-based polymerizable monomers having at least one structure selected from the group consisting of polyester, polycarbonate, polyurethane, polyether, polyconjugated diene, and hydrogenated polyconjugated diene (hereinafter, these are also referred to as "polymer skeletons") in one molecule, and urethane-modified (meth)acrylate-based polymerizable monomers without a polymer skeleton. These impart strength and ion release properties to the hardened material of dental filling and restorative materials. It is presumed that the urethane bond forms a hydrogen bond, not only exhibiting strength, but also promoting the propagation of ions with strong polarity, thereby exhibiting ion release properties.
[0061] The monofunctional polymerizable monomer having a urethane bond in one molecule can be easily synthesized, for example, by addition reaction of a compound containing an isocyanate having an alkylene skeleton or a phenylene skeleton with a (meth)acrylate compound having a hydroxyl group (-OH). It can also be easily synthesized by addition reaction of a polyol containing a polymer skeleton with a compound having an isocyanate group (-NCO) and a (meth)acrylate compound having a hydroxyl group (-OH). Among these, it is preferable that the dental filling and restorative material does not contain a polymer skeleton because the hardened material has excellent strength.
[0062] Examples of compounds having an isocyanate group include methylene diisocyanate (abbreviation: MDI), hexamethylene diisocyanate (abbreviation: HDI), isophorone diisocyanate (abbreviation: IPDI), trimethylhexamethylene diisocyanate (abbreviation: TMHMDI), tricyclodecane diisocyanate (abbreviation: TCDDI), adamantane diisocyanate (abbreviation: ADI), tolylene diisocyanate (abbreviation: TDI), xylylene diisocyanate (abbreviation: XDI), and diphenylmethane diisocyanate (abbreviation: DPMDI). Among these, from the viewpoint of excellent strength of the cured product of the dental filling and restorative material, IPDI, TMHMDI, and TCDDI are preferred, and TMHMDI is more preferred.
[0063] Examples of (meth)acrylate compounds having a hydroxyl group include hydroxy(meth)acrylate compounds such as 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, 6-hydroxyhexyl (meth)acrylate, 10-hydroxydecyl (meth)acrylate, 3-chloro-2-hydroxypropyl (meth)acrylate, 2-hydroxy-3-phenoxypropyl (meth)acrylate, glycerin mono(meth)acrylate, 2-hydroxy-3-acryloyloxypropyl (meth)acrylate, 2,2-bis[4-[3-(meth)acryloyloxy-2-hydroxypropoxy]phenyl]propane, 1,2-bis[3-(meth)acryloyloxy-2-hydroxypropoxy]ethane, pentaerythritol tri(meth)acrylate, and dipentaerythritol tri- or tetra(meth)acrylate. These may be used alone or in combination of two or more. Among these, from the viewpoint of excellent hardening property of the dental filling and restoring material, 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, and 2-hydroxy-3-acryloyloxypropyl (meth)acrylate are preferred, and 2-hydroxyethyl (meth)acrylate is more preferred.
[0064] The addition reaction between a compound having an isocyanate group and a (meth)acrylate compound having a hydroxyl group can be carried out according to a known method, and there is no particular limitation.
[0065] Examples of urethane-based (meth)acrylate polymerizable monomers that do not have a polymer backbone include 2,2,4-trimethylhexamethylenebis(2-carbamoyloxyethyl)dimethacrylate (abbreviation: UDMA); 2,4-tolylenebis(2-carbamoyloxyethyl)dimethacrylate; bishydroxyethylmethacrylate-isophorone diurethane; 2,4-tolylenebis(2-carbamoyloxyethyl)dimethacrylate; N,N'-(2,2,4-trimethylhexamethylene)bis[2-(aminocarboxy)propane-1,3-diol]tetramethacrylate (abbreviation: U4TH); hexamethylenebis{2-carbamoyloxy-3-phenoxypropyl}diacrylate; and 2,4-tolylenebis(2-carbamoyloxyethyl)hexaacrylate. These may be used alone or in combination of two or more. Among these, from the viewpoint of improving strength and ion release properties, UDMA and U4TH are preferred, and UDMA is more preferred.
[0066] In the above dental filling and restoring material, the content of the urethane-type (meth)acrylate-based polymerizable monomer not having a polymer skeleton is preferably 15 to 95 parts by mass, and from the viewpoint of excellent ion release property, is more preferably 18 to 90 parts by mass, even more preferably 20 to 80 parts by mass, even more preferably 22 to 70 parts by mass, even more preferably 22 to 60 parts by mass, and even more preferably 22 to 50 parts by mass, per 100 parts by mass of the total mass of the polymerizable monomer (C).
[0067] Examples of polyfunctional polymerizable monomers that do not contain any of a hydroxyl group, an acidic group, an amino group, an amide group, and a urethane bond in one molecule include an aromatic compound-based polyfunctional polymerizable monomer that contains two (meth)acryloyloxy groups in one molecule and does not contain any of a hydroxyl group, an acidic group, an amino group, an amide group, and a urethane bond; an aliphatic compound-based polyfunctional polymerizable monomer that contains two (meth)acryloyloxy groups in one molecule and does not contain any of a hydroxyl group, an acidic group, an amino group, an amide group, and a urethane bond; and a polyfunctional polymerizable monomer that contains three or more (meth)acryloyloxy groups in one molecule and does not contain any of a hydroxyl group, an acidic group, an amino group, an amide group, and a urethane bond.
[0068] Examples of the aromatic compound-based polyfunctional polymerizable monomer containing two (meth)acryloyloxy groups in one molecule and not containing any of a hydroxyl group, an acidic group, an amino group, an amide group, and a urethane bond include 2,2-bis((meth)acryloyloxyphenyl)propane; 2,2-bis(4-(meth)acryloyloxyethoxyphenyl)propane; 2,2-bis(4-(meth)acryloyloxypolyethoxyphenyl)propane; 2,2-bis(4-(meth)acryloyloxydiethoxyphenyl)propane; 2,2-bis(4-(meth)acryloyloxytetraethoxyphenyl)propane; 2,2-bis(4-(meth)acryloyloxypentaethoxyphenyl)propane; 2-(4-(meth)acryloyloxydipropoxyphenyl)propane; 2-(4-(meth)acryloyloxydiethoxyphenyl)-2-(4-(meth)acryloyloxyethoxyphenyl)propane; 2-(4-(meth)acryloyloxydiethoxyphenyl)-2-(4-(meth)acryloyloxyditriethoxyphenyl)propane; 2-(4-(meth)acryloyloxydipropoxyphenyl)-2-(4-(meth)acryloyloxytriethoxyphenyl)propane; 2,2-bis(4-(meth)acryloyloxypropoxyphenyl)propane; 2,2-bis(4-(meth)acryloyloxyisopropoxyphenyl)propane; and 1,4-bis(2-(meth)acryloyloxyethyl)pyromellitate. These may be used alone or in combination of two or more.
[0069] Examples of the aliphatic compound-based polyfunctional polymerizable monomer containing two (meth)acryloyloxy groups in one molecule and not containing any of a hydroxyl group, an acidic group, an amino group, an amide group, and a urethane bond include ethylene glycol di(meth)acrylate; diethylene glycol di(meth)acrylate; triethylene glycol di(meth)acrylate; propylene glycol di(meth)acrylate; butylene glycol di(meth)acrylate; neopentyl glycol di(meth)acrylate; polyethylene glycol di(meth)acrylate; 1,3-butanediol di(meth)acrylate; 1,4-butanediol di(meth)acrylate; 1,6-hexanediol di(meth)acrylate; 2-ethyl-1,6-hexanediol di(meth)acrylate; 1,9-nonanediol di(meth)acrylate; and 1,10-decanediol di(meth)acrylate. These may be used alone or in combination of two or more.
[0070] Examples of the polyfunctional polymerizable monomer containing three or more (meth)acryloyloxy groups in one molecule and not containing any of hydroxyl group, acid group, amino group, amide group and urethane bond include trimethylolpropane tri(meth)acrylate, trimethylolethane tri(meth)acrylate, trimethylolmethane tri(meth)acrylate, pentaerythritol tetra(meth)acrylate, dipentaerythritol penta(meth)acrylate and 1,7-diacryloyloxy-2,2,6,6-tetraacryloyloxymethyl-4-oxyheptane. These may be used alone or in combination of two or more.
[0071] In the above dental filling and restoring material, the content of the polyfunctional polymerizable monomer that does not contain any of a hydroxyl group, an acidic group, an amino group, an amide group, and a urethane bond is preferably 40 parts by mass or less, per 100 parts by mass of the total mass of the polymerizable monomer (C). From the viewpoint of better ion release properties, the content is more preferably 37 parts by mass or less, even more preferably 35 parts by mass or less, and even more preferably 33 parts by mass or less.
[0072] The polymerizable monomer (C) preferably contains a polymerizable monomer having any one of a hydroxyl group, an acid group, an amino group, an amide group, and a urethane bond. The polymerizable monomer may be a monofunctional polymerizable monomer or a polyfunctional polymerizable monomer. For example, from the viewpoint of sustained ion release, a polymerizable monomer having a urethane bond is preferred, and from the viewpoint of adhesion to tooth structure, a polymerizable monomer having a hydroxyl group is preferred. From the viewpoint of having both, it is more preferable to use a polymerizable monomer having a urethane bond and a polymerizable monomer having a hydroxyl group in combination.
[0073] The content of the polymerizable monomer having any one of a hydroxyl group, an acid group, an amino group, an amide group, and a urethane bond in the polymerizable monomer (C) is preferably 30 parts by mass or more, more preferably 40 parts by mass or more, and from the viewpoint of further excellent ion release property, more preferably 50 parts by mass or more, even more preferably 60 parts by mass or more, in the total mass 100 parts by mass of the polymerizable monomer (C), the content of the polymerizable monomer having any one of a hydroxyl group, an acid group, an amino group, an amide group, and a urethane bond in the polymerizable monomer (C) is 100 parts by mass or less, preferably 98 parts by mass or less, more preferably 96 parts by mass or less, even more preferably 94 parts by mass or less, and even more preferably 92 parts by mass or less, in the total mass 100 parts by mass of the polymerizable monomer (C). In other words, the content of the polymerizable monomer having any one of a hydroxyl group, an acidic group, an amino group, an amide group, and a urethane bond in the polymerizable monomer (C) is preferably 30 to 100 parts by mass in 100 parts by mass of the total mass of the polymerizable monomer (C).
[0074] From the viewpoints of sustained ion release and adhesion to tooth structure, the polymerizable monomer (C) preferably contains a (meth)acrylic compound (c-1) having at least one group or bond selected from the group consisting of a hydroxyl group, a carboxylic acid group, an amino group, an amide group, and a urethane bond (hereinafter also referred to as "(meth)acrylic compound (c-1)"). Examples of the (meth)acrylic compound containing a hydroxyl group include the compounds exemplified above as "monofunctional polymerizable monomers having a hydroxyl group in one molecule" and the compounds exemplified above as "polyfunctional polymerizable monomers having a hydroxyl group in one molecule". Examples of the (meth)acrylic compound containing a carboxylic acid group include the compounds exemplified above as the "polymerizable monomer having one carboxyl group in the molecule" and the compounds exemplified above as the "polymerizable monomer having multiple carboxyl groups in the molecule". Examples of the (meth)acrylic compound containing an amino group include the compounds exemplified above as the "monofunctional polymerizable monomer having an amino group in one molecule" and the compounds exemplified above as the "polyfunctional polymerizable monomer having an amino group in one molecule". Examples of the (meth)acrylic compound containing an amide group include the compounds exemplified above as the "monofunctional polymerizable monomer having an amide group in one molecule" and the compounds exemplified above as the "polyfunctional polymerizable monomer having an amide group in one molecule". Examples of the (meth)acrylic compound containing a urethane bond include the compounds exemplified above as the "polyfunctional polymerizable monomer having a urethane bond in one molecule".
[0075] The content of the (meth)acrylic compound (c-1) in the polymerizable monomer (C) is preferably 30 parts by mass or more, more preferably 40 parts by mass or more, and from the viewpoint of further excellent ion release property, more preferably 50 parts by mass or more, and even more preferably 60 parts by mass or more, in the total mass 100 parts by mass of the polymerizable monomer (C). The content of the (meth)acrylic compound (c-1) in the polymerizable monomer (C) is 100 parts by mass or less, preferably 98 parts by mass or less, more preferably 96 parts by mass or less, even more preferably 94 parts by mass or less, and even more preferably 92 parts by mass or less, in the total mass 100 parts by mass of the polymerizable monomer (C). In other words, the content of the (meth)acrylic compound (c-1) in the polymerizable monomer (C) is preferably 30 to 100 parts by mass in the total mass 100 parts by mass of the polymerizable monomer (C).
[0076] <Content of components (A) to (C)> In order to ensure good aesthetics, high strength, and high tooth structure strengthening ability, the total mass of the organic fluorinating agent (A), the ion-releasing glass (B), and the polymerizable monomer (C) in the dental filling and restoring material is preferably 60 to 100 mass% or more, more preferably 65 to 99 mass% or more, even more preferably 70 to 99 mass% or more, and still more preferably 75 to 99 mass% or more, based on the total mass of the dental filling and restoring material.
[0077] <Polymerization initiator> The polymerization initiator can be selected from polymerization initiators used in general industry, and among them, polymerization initiators used for dental applications are preferably used. The polymerization initiator preferably contains at least one selected from the group consisting of chemical polymerization initiators and photopolymerization initiators, more preferably contains at least a chemical polymerization initiator, and may contain both a chemical polymerization initiator and a photopolymerization initiator.
[0078] (Chemical polymerization initiators and peroxides (D)) Examples of chemical polymerization initiators include organic peroxides, inorganic peroxides, and transition metal complexes. These are not particularly limited and known ones can be used. The organic peroxides, inorganic peroxides, and transition metal complexes may be blended alone or in combination of two or more. Hereinafter, the above organic peroxides and inorganic peroxides are collectively referred to as "peroxide (D)". From the viewpoint of reducing polymerization shrinkage stress, the above dental filling and restorative material preferably further contains a peroxide (D). The organic peroxide used as the chemical polymerization initiator is not particularly limited, and known organic peroxides can be used. Representative organic peroxides include, for example, ketone peroxides, hydroperoxides, diacyl peroxides, dialkyl peroxides, peroxyketals, peroxyesters, and peroxydicarbonates. These may be used alone or in combination of two or more.
[0079] Examples of the ketone peroxide include methyl ethyl ketone peroxide, methyl isobutyl ketone peroxide, methylcyclohexanone peroxide, and cyclohexanone peroxide.
[0080] Examples of the hydroperoxide include 2,5-dimethylhexane-2,5-dihydroperoxide; diisopropylbenzene hydroperoxide; cumene hydroperoxide; t-butyl hydroperoxide; and 1,1,3,3-tetramethylbutyl hydroperoxide (abbreviation: THP).
[0081] Examples of the diacyl peroxide include acetyl peroxide, isobutyryl peroxide, benzoyl peroxide (abbreviation: BPO), decanoyl peroxide, 3,5,5-trimethylhexanoyl peroxide, 2,4-dichlorobenzoyl peroxide, and lauroyl peroxide.
[0082] Examples of the dialkyl peroxide include di-t-butyl peroxide, dicumyl peroxide, t-butylcumyl peroxide, 2,5-dimethyl-2,5-di(t-butylperoxy)hexane, 1,3-bis(t-butylperoxyisopropyl)benzene, and 2,5-dimethyl-2,5-di(t-butylperoxy)-3-hexyne.
[0083] Examples of such peroxyketals include 1,1-bis(t-butylperoxy)-3,3,5-trimethylcyclohexane; 1,1-bis(t-butylperoxy)cyclohexane; 2,2-bis(t-butylperoxy)butane; 2,2-bis(t-butylperoxy)octane; and 4,4-bis(t-butylperoxy)valeric acid n-butyl ester.
[0084] Examples of the peroxy esters include α-cumyl peroxyneodecanoate; t-butyl peroxyneodecanoate; t-butyl peroxypivalate; 2,2,4-trimethylpentyl peroxy-2-ethylhexanoate; t-amyl peroxy-2-ethylhexanoate; t-butyl peroxy-2-ethylhexanoate; di-t-butylperoxyisophthalate; di-t-butylperoxyhexahydroterephthalate; t-butylperoxy-3,3,5-trimethylhexanoate; t-butyl peroxyacetate; t-butyl peroxybenzoate; and t-butyl peroxymaleate.
[0085] Examples of the peroxydicarbonate include di-3-methoxyperoxydicarbonate; di-2-ethylhexyl peroxydicarbonate; bis(4-t-butylcyclohexyl) peroxydicarbonate; diisopropyl peroxydicarbonate; di-n-propyl peroxydicarbonate; di-2-ethoxyethyl peroxydicarbonate; and diallyl peroxydicarbonate.
[0086] Among these organic peroxides, from the viewpoint of the overall balance of safety, curability, and storage stability, the chemical polymerization initiator is preferably one selected from hydroperoxides and diacyl peroxides, and more preferably hydroperoxides. Among them, the chemical polymerization initiator is preferably one or more selected from the group consisting of benzoyl peroxide, cumene hydroperoxide, t-butyl hydroperoxide, and 1,1,3,3-tetramethylbutyl hydroperoxide, more preferably one or more selected from the group consisting of cumene hydroperoxide, t-butyl hydroperoxide, and 1,1,3,3-tetramethylbutyl hydroperoxide, and more preferably 1,1,3,3-tetramethylbutyl hydroperoxide.
[0087] Examples of inorganic oxides include peroxodisulfates and peroxodiphosphates, and among these, peroxodisulfates are preferred in terms of curability. Specific examples of peroxodisulfates include sodium peroxodisulfate, potassium peroxodisulfate, aluminum peroxodisulfate, and ammonium peroxodisulfate.
[0088] From the viewpoint of curing property, the amount of the peroxide (D) is preferably 0.01 to 5 parts by mass, and more preferably 0.05 to 2 parts by mass, per 100 parts by mass of the total mass of the polymerizable monomer (C) in the dental filling and restorative material.
[0089] (Photopolymerization initiator) Examples of photopolymerization initiators include (bis)acylphosphine oxides (including salts), thioxanthones (including salts such as quaternary ammonium salts), ketals, α-diketones, coumarins, anthraquinones, benzoin alkyl ether compounds, and α-aminoketone compounds. These may be used alone or in combination of two or more.
[0090] Among these photopolymerization initiators, it is preferable to use at least one selected from the group consisting of (bis)acylphosphine oxides and α-diketones, which provides a dental filling and restorative material that is excellent in photocurability in the visible light region and near ultraviolet region and exhibits sufficient photocurability when using any of the light sources, that is, a halogen lamp, a light-emitting diode (LED), and a xenon lamp.
[0091] Among the above (bis)acylphosphine oxides, examples of the acylphosphine oxides include 2,4,6-trimethylbenzoyldiphenylphosphine oxide; 2,6-dimethoxybenzoyldiphenylphosphine oxide; 2,6-dichlorobenzoyldiphenylphosphine oxide; 2,4,6-trimethylbenzoylmethoxyphenylphosphine oxide; 2,4,6-trimethylbenzoylethoxyphenylphosphine oxide; 2,3,5,6-tetramethylbenzoyldiphenylphosphine oxide; benzoyldi(2,6-dimethylphenyl)phosphonate; sodium salt of 2,4,6-trimethylbenzoylphenylphosphine oxide; potassium salt of 2,4,6-trimethylbenzoylphenylphosphine oxide; and ammonium salt of 2,4,6-trimethylbenzoylphenylphosphine oxide.
[0092] Among the above (bis)acylphosphine oxides, examples of the bisacylphosphine oxides include bis(2,6-dichlorobenzoyl)phenylphosphine oxide; bis(2,6-dichlorobenzoyl)-2,5-dimethylphenylphosphine oxide; bis(2,6-dichlorobenzoyl)-4-propylphenylphosphine oxide; bis(2,6-dichlorobenzoyl)-1-naphthylphosphine oxide; bis(2,6-dimethoxybenzoyl)phenylphosphine oxide; bis(2,6-dimethoxybenzoyl)-2,4,4-trimethylpentylphosphine oxide; bis(2,6-dimethoxybenzoyl)-2,5-dimethylphenylphosphine oxide; bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide (abbreviation: BAPO); and bis(2,3,6-trimethylbenzoyl)-2,4,4-trimethylpentylphosphine oxide.
[0093] Further examples of the (bis)acylphosphine oxides include the compounds described in JP-A-2000-159621.
[0094] Among these (bis)acylphosphine oxides, it is more preferable to use 2,4,6-trimethylbenzoyldiphenylphosphine oxide, 2,4,6-trimethylbenzoylmethoxyphenylphosphine oxide, bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide, and the sodium salt of 2,4,6-trimethylbenzoylphenylphosphine oxide as the photopolymerization initiator.
[0095] Examples of the α-diketones include diacetyl, benzyl, camphorquinone (abbreviation: CQ), 2,3-pentadione, 2,3-octadione, 9,10-phenanthrenequinone, 4,4'-oxybenzyl, and acenaphthenequinone. Among these, camphorquinone is particularly preferred from the viewpoint of having a maximum absorption wavelength in the visible light region.
[0096] The content of the polymerization initiator is not particularly limited, but from the viewpoint of the hardening property of the dental filling and restoring material, it is preferably contained in an amount of 0.001 to 30 parts by mass relative to 100 parts by mass of the total mass of the polymerizable monomer (C). By the content of the polymerization initiator being 0.001 parts by mass or more, polymerization can be sufficiently advanced and stickiness can be prevented. From this viewpoint, the content of the polymerization initiator is more preferably 0.03 parts by mass or more, even more preferably 0.05 parts by mass or more, and even more preferably 0.1 parts by mass or more, relative to 100 parts by mass of the total mass of the polymerizable monomer (C). On the other hand, by the content of the polymerization initiator being 30 parts by mass or less, precipitation or separation of the polymerization initiator from the dental filling and restoring material can be prevented. From this viewpoint, the content of the polymerization initiator is more preferably 10 parts by mass or less, even more preferably 5 parts by mass or less, and even more preferably 2 parts by mass or less, relative to 100 parts by mass of the total mass of the polymerizable monomer (C).
[0097] Furthermore, when the polymerization initiator contains a chemical polymerization initiator, the content of the chemical polymerization initiator is not particularly limited, but in one embodiment of the above-mentioned dental filling and restorative material, from the viewpoint of more easily achieving the effects of the present invention, the mass of the chemical polymerization initiator in the polymerization initiator is preferably 60 to 100 mass%, more preferably 70 to 100 mass%, and even more preferably 80 to 100 mass%, in 100 mass% of the polymerization initiator.
[0098] Furthermore, when the polymerization initiator contains a photopolymerization initiator, the mass of the photopolymerization initiator is not particularly limited, but in one embodiment of the above-mentioned dental filling and restorative material, from the viewpoint of making it easier to achieve the effects of the present invention, the content of the photopolymerization initiator in the polymerization initiator is preferably 1 to 100 mass%, more preferably 5 to 60 mass%, and even more preferably 10 to 30 mass%, in 100 mass% of the polymerization initiator.
[0099] In addition, in one embodiment of the above dental filling and restorative material, from the viewpoint of making it easier to achieve the effects of the present invention, the total content of the chemical polymerization initiator and the photopolymerization initiator in the polymerization initiator is preferably 30 to 100 mass%, more preferably 50 to 100 mass%, even more preferably 80 to 100 mass%, and may be 100 mass%, based on 100 mass% of the total mass of the polymerization initiator.
[0100] <Polymerization accelerator> The dental filling and restoring material preferably further contains a polymerization accelerator. Examples of the polymerization accelerator include amines, sulfinic acid and its salt, sulfur-containing reductive inorganic compounds, aldehydes, thiourea compounds, organic phosphorus compounds, borate compounds, barbituric acids and their derivatives, triazine compounds, transition metal complexes, benzotriazole compounds, benzimidazole compounds, halogen compounds, and thiol compounds. These may be used alone or in combination of two or more.
[0101] Amines are divided into aliphatic amines and aromatic amines. Examples of aliphatic amines include primary aliphatic amines such as n-butylamine, n-hexylamine, and n-octylamine; secondary aliphatic amines such as diisopropylamine, dibutylamine, and N-methylethanolamine; and tertiary aliphatic amines such as N-methyldiethanolamine (abbreviation: NMDEA), N-ethyldiethanolamine, Nn-butyldiethanolamine, N-lauryldiethanolamine, 2-(dimethylamino)ethyl methacrylate, N-methyldiethanolamine dimethacrylate, N-ethyldiethanolamine dimethacrylate, triethanolamine monomethacrylate, triethanolamine dimethacrylate, triethanolamine trimethacrylate, triethanolamine, trimethylamine, triethylamine, and tributylamine. Among these, tertiary aliphatic amines are preferred in terms of redox reactivity, and N-methyldiethanolamine (abbreviation: NMDEA), triethanolamine, and 2-(dimethylamino)ethyl methacrylate are particularly preferred.
[0102] Examples of aromatic amines include N,N-bis(2-hydroxyethyl)-3,5-dimethylaniline; N,N-bis(2-hydroxyethyl)-p-toluidine; N,N-bis(2-hydroxyethyl)-3,4-dimethylaniline; N,N-bis(2-hydroxyethyl)-4-ethylaniline; N,N-bis(2-hydroxyethyl)-4-isopropylaniline; N,N-bis(2-hydroxyethyl)-4-t-butylaniline; N,N-bis(2-hydroxyethyl)-3,5-di-isopropylaniline; N,N-bis(2-hydroxyethyl)-3,5-di-t-butylaniline; N,N-dimethylaniline; N,N-dimethyl-p-toluidine; N,N-dimethyl-m-toluidine; N,N- Diethyl-p-toluidine; N,N-dimethyl-3,5-dimethylaniline; N,N-dimethyl-3,4-dimethylaniline; N,N-dimethyl-4-ethylaniline; N,N-dimethyl-4-isopropylaniline; N,N-dimethyl-4-t-butylaniline; N,N-dimethyl-3,5-di-t-butylaniline; 4-(N,N-dimethylamino)ethyl benzoate (abbreviation: PDE); 4-(N,N-dimethylamino)methyl benzoate; 4-(N,N-dimethylamino)n-butoxyethyl benzoate; 4-(N,N-dimethylamino)2-(methacryloyloxy)ethyl benzoate; 4-(N,N-dimethylamino)benzophenone; and 4-(N,N-dimethylamino)butyl benzoate. Among these, from the viewpoint of imparting excellent hardening properties to the dental filling and restorative material, at least one selected from the group consisting of N,N-bis(2-hydroxyethyl)-p-toluidine, ethyl 4-(N,N-dimethylamino)benzoate (abbreviation: PDE), n-butoxyethyl 4-(N,N-dimethylamino)benzoate, and 4-(N,N-dimethylamino)benzophenone is preferably used.
[0103] The mass of the aromatic amine or aliphatic amine in the dental filling and restoring material is preferably 0.01 to 10 parts by mass, more preferably 0.02 to 5 parts by mass, and even more preferably 0.05 to 2 parts by mass, relative to 100 parts by mass of the total mass of the polymerizable monomer (C) in the dental filling and restoring material. If the mass is 0.01 parts by mass or more, it is easy to prevent the adhesive strength of the obtained dental filling and restoring material to a wet body such as a tooth substance from decreasing. On the other hand, if the mass is 10 parts by mass or less, it is easy to prevent the color stability of the obtained dental filling and restoring material from decreasing.
[0104] Examples of sulfinic acids and their salts include p-toluenesulfinic acid, p-toluenesulfinic acid, o-toluenesulfinic acid, benzenesulfinic acid, ethylbenzenesulfinic acid, decylbenzenesulfinic acid, dodecylbenzenesulfinic acid, 2,4,6-trimethylbenzenesulfinic acid, 2,4,6-triethylbenzenesulfinic acid, 2,4,6-triisopropylbenzenesulfinic acid, chlorobenzenesulfinic acid, naphthalenesulfinic acid, and their lithium salts, sodium salts, potassium salts, rubidium salts, cesium salts, magnesium salts, calcium salts, strontium salts, iron salts, zinc salts, ammonium salts, tetramethylammonium salts, and tetraethylammonium salts. Among these, from the viewpoint of the hardening property and storage stability of dental filling and restorative materials, the lithium salt, sodium salt, potassium salt, magnesium salt, and calcium salt of 2,4,6-trimethylbenzenesulfinic acid and 2,4,6-triisopropylbenzenesulfinic acid are preferred, and the lithium salt, sodium salt, potassium salt, magnesium salt, and calcium salt of 2,4,6-triisopropylbenzenesulfinic acid are more preferred.
[0105] It is preferable that at least a part of the sulfinate is dispersed in the dental filling and restoring material in the form of a powder. By dispersing in the form of a powder, the dental filling and restoring material can ensure a longer operation time, and when applied to a wet body such as a tooth, the sulfinate dissolves in water on the surface of the wet body, so that the polymerization curing property at the adhesive interface and inside the resin-impregnated layer can be further enhanced. When dispersing the sulfinate in the form of a powder, the sulfinate preferably has a solubility in water at room temperature (25°C) of 1 mg / 100 mL or more. If the solubility is less than 1 mg / 100 mL, when the dental filling and restoring material is applied to a wet body, the sulfinate does not dissolve sufficiently in the water of the wet body at the adhesive interface, and as a result, the effect of dispersing in the form of a powder is difficult to be expressed. In addition, since the sulfinate is prone to settling if its particle size is too large, the average particle size is preferably 500 μm or less, more preferably 100 μm or less, and even more preferably 50 μm or less. In order to avoid the deterioration of the handling property of the dental filling and restorative material due to the excessively large specific surface area of the powder, the average particle size is preferably 0.01 μm or more. That is, the average particle size in the case of dispersion in powder is preferably in the range of 0.01 to 500 μm, more preferably in the range of 0.01 to 100 μm. In this specification, the average particle size refers to the volume average particle size, and the volume average particle size can be calculated, for example, by performing image analysis using image analysis software (e.g., Mac-View; manufactured by Mountec Co., Ltd.) based on an electron microscope photograph of 100 or more particles.
[0106] When the sulfinate is dispersed in powder form, the shape may be, but is not limited to, various shapes such as spheres, needles, plates, crushed shapes, etc. The sulfinate can be prepared into a fine powder by a conventionally known method such as a pulverization method or a freeze-drying method.
[0107] The mass of the sulfinate in the dental filling and restoring material is preferably 0.1 to 5 parts by mass, more preferably 0.2 to 4 parts by mass, and most preferably 0.5 to 3 parts by mass, relative to 100 parts by mass of the total mass of the polymerizable monomer (C) in the dental filling and restoring material. When the mass is 0.1 parts by mass or more and 5 parts by mass or less, the mechanical strength of the hardened product of the dental filling and restoring material obtained is easily ensured.
[0108] Examples of reducing inorganic compounds having sulfur include sulfites, bisulfites, pyrosulfites, thiosulfates, thionates, and dithionites. Of these, sulfites and bisulfites are preferred. Specific examples include sodium sulfite, potassium sulfite, calcium sulfite, ammonium sulfite, sodium hydrogen sulfite, and potassium hydrogen sulfite. One type may be used alone, or two or more types may be used in combination.
[0109] It is preferable that at least a part of the reducible inorganic compound containing sulfur is dispersed in the dental filling and restoring material in the form of a powder. By dispersing the reducible inorganic compound containing sulfur in the form of a powder, the dental filling and restoring material can ensure a longer operation time, and when applied to a wet body such as a tooth, the reducible inorganic compound dissolves in water on the surface of the wet body, so that the polymerization curing property at the adhesive interface and inside the resin-impregnated layer can be further enhanced. When dispersing the reducible inorganic compound in the form of a powder, the reducible inorganic compound preferably has a solubility in water at room temperature (25°C) of 1 mg / 100 mL or more. If the solubility is less than 1 mg / 100 mL, when the dental filling and restoring material is applied to a wet body, the reducible inorganic compound does not dissolve sufficiently in the water of the wet body at the adhesive interface, and as a result, the effect of dispersing in the form of a powder is difficult to be expressed. In addition, since the reducible inorganic compound is prone to settling if its particle size is too large, the average particle size is preferably 500 μm or less, more preferably 100 μm or less, and even more preferably 50 μm or less. In order to avoid the specific surface area of the powder becoming too large and the handling of the dental filling and restorative material becoming poor, the average particle size is preferably 0.01 μm or more. That is, the average particle size in the case of dispersion in powder is preferably in the range of 0.01 to 500 μm, more preferably in the range of 0.01 to 100 μm. The average particle size can be measured in the same manner as the average particle size of the sulfinic acid salt described above.
[0110] When the reducing inorganic compound is dispersed in the form of a powder, the shape of the reducing inorganic compound is not particularly limited, and may be, for example, spherical, needle-like, plate-like, crushed, etc. The reducing inorganic compound can be prepared into a fine powder by a conventionally known method such as a pulverization method or a freeze-drying method.
[0111] The mass of the reducing inorganic compound of the dental filling and restoring material is preferably 0.01 to 15 parts by mass, more preferably 0.05 to 10 parts by mass, and most preferably 0.1 to 5 parts by mass, relative to 100 parts by mass of the total mass of the polymerizable monomer (C) in the dental filling and restoring material. If the mass is 0.01 parts by mass or more, it is easy to prevent the adhesive strength of the obtained dental filling and restoring material to a wet body such as a tooth substance from decreasing. On the other hand, if the mass is 15 parts by mass or less, it is easy to ensure the mechanical strength of the hardened product of the obtained dental filling and restoring material.
[0112] Examples of aldehydes include terephthalaldehyde and benzaldehyde derivatives. Examples of benzaldehyde derivatives include dimethylaminobenzaldehyde, p-methyloxybenzaldehyde, and p-ethyloxybenzaldehyde and pn-octyloxybenzaldehyde (abbreviation: OBA). One type may be used alone, or two or more types may be used in combination.
[0113] Examples of thiourea compounds include 1-(2-pyridyl)-2-thiourea (abbreviation: pyTU); thiourea; methylthiourea; ethylthiourea; N,N'-dimethylthiourea; N,N'-diethylthiourea; N,N'-di-n-propylthiourea; N,N'-dicyclohexylthiourea; trimethylthiourea; triethylthiourea; tri-n-propylthiourea; tricyclohexylthiourea; tetramethylthiourea; tetraethylthiourea; tetra-n-propylthiourea; tetracyclohexylthiourea; ethylenethiourea; 3,3-dimethylethylenethiourea; 4,4-dimethylethylenethiourea (abbreviation: DMETU); N-acetylthiourea; N-benzoylthiourea; and diphenylthiourea. Among these, from the viewpoint of the hardening property of the dental filling and restorative material, at least one selected from the group consisting of 1-(2-pyridyl)-2-thiourea, 4,4-dimethylethylenethiourea, and benzoylthiourea is preferably used.
[0114] Examples of organophosphorus compounds include triphenylphosphine; 2-methyltriphenylphosphine; 4-methyltriphenylphosphine; 2-methoxytriphenylphosphine; 4-methoxytriphenylphosphine; tri-n-butylphosphine; triisobutylphosphine; and tri-t-butylphosphine.
[0115] The borate compound is preferably an aryl borate compound.Specific examples of the aryl borate compound that can be suitably used include borate compounds having one aryl group in one molecule, such as trialkylphenyl boron; trialkyl(p-chlorophenyl) boron; trialkyl(p-fluorophenyl) boron; trialkyl[3,5-bis(trifluoromethyl)phenyl] boron; trialkyl[3,5-bis(1,1,1,3,3,3-hexafluoro-2-methoxy-2-propyl)phenyl] boron; trialkyl(p-nitrophenyl) boron; trialkyl(m-nitrophenyl) boron; trialkyl(p-butylphenyl) boron; trialkyl(m-butylphenyl) boron; trialkyl Examples of such compounds include (p-butyloxyphenyl)boron; trialkyl(m-butyloxyphenyl)boron; trialkyl(p-octyloxyphenyl)boron; trialkyl(m-octyloxyphenyl)boron (wherein the alkyl group is at least one selected from the group consisting of an n-butyl group, an n-octyl group, and an n-dodecyl group); and salts thereof (such as sodium salts, lithium salts, potassium salts, magnesium salts, tetrabutylammonium salts, tetramethylammonium salts, tetraethylammonium salts, methylpyridinium salts, ethylpyridinium salts, butylpyridinium salts, methylquinolinium salts, ethylquinolinium salts, and butylquinolinium salts).
[0116] Examples of borate compounds having two aryl groups in one molecule include dialkyldiphenylboron; dialkyldi(p-chlorophenyl)boron; dialkyldi(p-fluorophenyl)boron; dialkyldi[3,5-bis(trifluoromethyl)phenyl]boron; dialkyldi[3,5-bis(1,1,1,3,3,3-hexafluoro-2-methoxy-2-propyl)phenyl]boron; dialkyldi(p-nitrophenyl)boron; dialkyldi(m-nitrophenyl)boron; dialkyldi(p-butylphenyl)boron; dialkyldi(m-butylphenyl)boron; dialkyldi(p-butyloxyphenyl)boron. dialkyldi(m-butyloxyphenyl)boron; dialkyldi(p-octyloxyphenyl)boron and dialkyldi(m-octyloxyphenyl)boron (wherein the alkyl group is at least one selected from the group consisting of an n-butyl group, an n-octyl group, an n-dodecyl group, and the like); and salts thereof (sodium salt, lithium salt, potassium salt, magnesium salt, tetrabutylammonium salt, tetramethylammonium salt, tetraethylammonium salt, methylpyridinium salt, ethylpyridinium salt, butylpyridinium salt, methylquinolinium salt, ethylquinolinium salt, butylquinolinium salt, and the like).
[0117] Examples of borate compounds having three aryl groups in one molecule include monoalkyltriphenylboron; monoalkyltri(p-chlorophenyl)boron; monoalkyltri(p-fluorophenyl)boron; monoalkyltri[3,5-bis(trifluoromethyl)phenyl]boron; monoalkyltri[3,5-bis(1,1,1,3,3,3-hexafluoro-2-methoxy-2-propyl)phenyl]boron; monoalkyltri(p-nitrophenyl)boron; monoalkyltri(m-nitrophenyl)boron; monoalkyltri(p-butylphenyl)boron; monoalkyltri(m-butylphenyl)boron; monoalkyltri(p-butylphenyl)boron. monoalkyltri(m-butyloxyphenyl)boron; monoalkyltri(p-octyloxyphenyl)boron; monoalkyltri(m-octyloxyphenyl)boron (wherein the alkyl group is one selected from an n-butyl group, an n-octyl group, and an n-dodecyl group); and salts thereof (sodium salt, lithium salt, potassium salt, magnesium salt, tetrabutylammonium salt, tetramethylammonium salt, tetraethylammonium salt, methylpyridinium salt, ethylpyridinium salt, butylpyridinium salt, methylquinolinium salt, ethylquinolinium salt, butylquinolinium salt, etc.).
[0118] Examples of borate compounds having four aryl groups in one molecule include tetraphenylboron; tetrakis(p-chlorophenyl)boron; tetrakis(p-fluorophenyl)boron; tetrakis[3,5-bis(trifluoromethyl)phenyl]boron; tetrakis[3,5-bis(1,1,1,3,3,3-hexafluoro-2-methoxy-2-propyl)phenyl]boron; tetrakis(p-nitrophenyl)boron; tetrakis(m-nitrophenyl)boron; tetrakis(p-butylphenyl)boron; tetrakis(m-butylphenyl)boron; tetrakis(p-butyloxyphenyl)boron; tetrakis(m-butyloxyphenyl)boron; tetrakis(p-octyloxyphenyl)boron; tetrakis(m-octyloxyphenyl)boron; [3,5-bis(trifluoromethyl)phenyl]triphenylboron; (p-nitrophenyl)triphenylboron; (m-butyloxyphenyl)triphenylboron; (p-butyloxyphenyl)triphenylboron; (m-octyloxyphenyl)triphenylboron; (p-octyloxyphenyl)triphenylboron; and salts thereof (sodium salts, lithium salts, potassium salts, magnesium salts, tetrabutylammonium salts, tetramethylammonium salts, tetraethylammonium salts, methylpyridinium salts, ethylpyridinium salts, butylpyridinium salts, methylquinolinium salts, ethylquinolinium salts, butylquinolinium salts, etc.).
[0119] Among these aryl borate compounds, it is more preferable to use a borate compound having 3 or 4 aryl groups in one molecule from the viewpoint of storage stability. Moreover, these aryl borate compounds can be used alone or in combination of two or more kinds.
[0120] Examples of barbituric acids and their derivatives include barbituric acid; 1,3-dimethylbarbituric acid; 1,3-diphenylbarbituric acid; 1,5-dimethylbarbituric acid; 5-butylbarbituric acid; 5-ethylbarbituric acid; 5-isopropylbarbituric acid; 5-cyclohexylbarbituric acid; 1,3,5-trimethylbarbituric acid; 1,3-dimethyl-5-ethylbarbituric acid; 1,3-dimethyl-5-n-butylbarbituric acid; 1,3-dimethyl-5-isobutylbarbituric acid; 1,3-dimethyl-5-cyclopentylbarbituric acid; 1,3-dimethyl-5-cyclohexylbarbituric acid; 1,3-dimethyl-5-phenylbarbituric acid; 1-cyclohexyl-1-ethylbarbituric acid. barbituric acid; 1-benzyl-5-phenylbarbituric acid; 5-methylbarbituric acid; 5-propylbarbituric acid; 1,5-diethylbarbituric acid; 1-ethyl-5-methylbarbituric acid; 1-ethyl-5-isobutylbarbituric acid; 1,3-diethyl-5-butylbarbituric acid; 1-cyclohexyl-5-methylbarbituric acid; 1-cyclohexyl-5-ethylbarbituric acid; 1-cyclohexyl-5-octylbarbituric acid; 1-cyclohexyl-5-hexylbarbituric acid; 5-butyl-1-cyclohexylbarbituric acid; 1-benzyl-5-phenylbarbituric acid; thiobarbituric acids; and salts thereof (particularly alkali metal or alkaline earth metal salts are preferred). Salts of these barbituric acids include, for example, sodium 5-butylbarbiturate; sodium 1,3,5-trimethylbarbiturate; and sodium 1-cyclohexyl-5-ethylbarbiturate.
[0121] Examples of triazine compounds include 2,4,6-tris(trichloromethyl)-s-triazine; 2,4,6-tris(tribromomethyl)-s-triazine; 2-methyl-4,6-bis(trichloromethyl)-s-triazine; 2-methyl-4,6-bis(tribromomethyl)-s-triazine; 2-phenyl-4,6-bis(trichloromethyl)-s-triazine; 2-(p-methoxyphenyl)-4,6-bis(trichloromethyl)-s-triazine; 2-(p-methylthiophenyl)-4,6-bis(trichloromethyl) -s-Triazine;2-(p-Chlorophenyl)-4,6-bis(trichloromethyl)-s-triazine;2-(2,4-dichlorophenyl)-4,6-bis(trichloromethyl)-s-triazine;2-(p-Bromophenyl)-4,6-bis(trichloromethyl)-s-triazine;2-(p-Tolyl)-4,6-bis(trichloromethyl)-s-triazine;2-n-Propyl-4,6-bis(trichloromethyl)-s-triazine;2-(α,α,β-Trichloroethyl)-4,6-bis(trichloromethyl)-s-triazine azine;2-Styryl-4,6-bis(trichloromethyl)-s-triazine;2-[2-(p-methoxyphenyl)ethenyl]-4,6-bis(trichloromethyl)-s-triazine;2-[2-(o-methoxyphenyl)ethenyl]-4,6-bis(trichloromethyl)-s-triazine;2-[2-(p-butoxyphenyl)ethenyl]-4,6-bis(trichloromethyl)-s-triazine;2-[2-(3,4-dimethoxyphenyl)ethenyl]-4,6-bis(trichloromethyl)-s-triazine;2-[2-( 3,4,5-trimethoxyphenyl)ethenyl]-4,6-bis(trichloromethyl)-s-triazine;2-(1-naphthyl)-4,6-bis(trichloromethyl)-s-triazine;2-(4-biphenylyl)-4,6-bis(trichloromethyl)-s-triazine;2-[2-{N,N-bis(2-hydroxyethyl)amino}ethoxy]-4,6-bis(trichloromethyl)-s-triazine;2-[2-{N-hydroxyethyl-N-ethylamino}ethoxy]-4,6-bis(trichloromethyl)-s-triazine;2-[2-{N-hydroxyethyl-N-methylamino}ethoxy]-4,6-bis(trichloromethyl)-s-triazine; and 2-[2-{N,N-diallylamino}ethoxy]-4,6-bis(trichloromethyl)-s-triazine.
[0122] The triazine compound may be used alone or in combination of two or more kinds as required. The mass of the triazine compound in the dental filling and restoring material is preferably 0.005 to 0.3 parts by mass, more preferably 0.008 to 0.2 parts by mass, and even more preferably 0.01 to 0.1 parts by mass, based on 100 parts by mass of the total mass of the polymerizable monomer (C) in the dental filling and restoring material.
[0123] Examples of the transition metal complex include vanadium compounds, copper compounds, tin compounds, and cobalt compounds.
[0124] The vanadium compound is preferably a tetravalent and / or pentavalent vanadium compound. Examples of tetravalent and / or pentavalent vanadium compounds include divanadium(IV) tetroxide, vanadium acetylacetonate, vanadyl acetylacetonate (VOAA), vanadyl stearate, vanadium naphthenate, vanadium benzoylacetonate, vanadyl oxalate, vanadyl sulfate, oxo-bis(1-phenyl-1,3-butanedionate)vanadium, bis(maltolato)oxovanadium, vanadium pentoxide, sodium metavanadate, and ammonium metavanadate. Among these, vanadium acetylacetonate and vanadyl acetylacetonate are preferred from the viewpoint of the hardening property of the dental filling and restorative material.
[0125] From the viewpoint of hardening property, the mass of the vanadium compound in the dental filling and restoring material is preferably 0.0001 to 1 part by mass per 100 parts by mass of the total mass of the polymerizable monomer (C) in the dental filling and restoring material.
[0126] The copper compound is preferably a compound soluble in the polymerizable monomer (C). Specific examples thereof include copper carboxylates such as copper (II) acetate (abbreviation: CuOA), copper isobutyrate, copper gluconate, copper citrate, copper phthalate, copper tartrate, copper oleate, copper octylate, copper octenate, copper naphthenate, copper methacrylate, and copper 4-cyclohexylbutyrate; and β-diketones such as copper acetylacetone, copper trifluoroacetylacetone, copper hexafluoroacetylacetone, and copper 2,2,6,6-tetramethyl- Examples of copper 3,5-heptanedionate include copper benzoylacetone; β-ketoester copper includes copper ethyl acetoacetate; copper alkoxides include copper methoxide, copper ethoxide, copper isopropoxide, copper 2-(2-butoxyethoxy)ethoxide, and copper 2-(2-methoxyethoxy)ethoxide; copper dithiocarbamate includes copper dimethyldithiocarbamate; salts of copper with inorganic acids include copper nitrate; and copper chloride and copper bromide. These can be used alone or in combination of two or more. Among these, from the viewpoints of solubility in polymerizable monomers and hardening properties of dental filling and restorative materials, copper carboxylate, copper β-diketone, and copper β-ketoester are preferred, and at least one selected from the group consisting of copper acetate (II) and copper acetylacetonate is preferably used.
[0127] From the viewpoint of hardening property, the mass of the copper compound in the dental filling and restoring material is preferably 0.000005 to 1 part by mass per 100 parts by mass of the total mass of the polymerizable monomer (C) in the dental filling and restoring material.
[0128] Examples of the tin compound include di-n-butyltin dimaleate, di-n-octyltin dimaleate, di-n-octyltin dilaurate, and di-n-butyltin dilaurate. Among them, at least one selected from the group consisting of di-n-octyltin dilaurate and di-n-butyltin dilaurate is preferably used. Examples of cobalt compounds include cobalt acetylacetonate, cobalt acetate, cobalt oleate, cobalt chloride, and cobalt bromide.
[0129] Benzotriazole compounds and / or benzimidazole compounds include, for example, compounds described in Japanese Patent No. 5,622,867.
[0130] Benzotriazole compounds and benzimidazole compounds may be used alone or in combination of two or more.Specific examples of benzotriazole compounds and benzimidazole compounds include 1H-benzotriazole; 5-methyl-1H-benzotriazole; 5,6-dimethyl-1H-benzotriazole; benzimidazole; 5-methylbenzimidazole; and 5,6-dimethylbenzimidazole.Among these, 1H-benzotriazole and 5-methyl-1H-benzotriazole are preferred in terms of color tone and storage stability of dental filling and restorative materials.
[0131] Examples of halogen compounds include dilauryl dimethyl ammonium chloride; lauryl dimethyl benzyl ammonium chloride; benzyl trimethyl ammonium chloride; tetramethyl ammonium chloride; benzyl dimethyl cetyl ammonium chloride; and dilauryl dimethyl ammonium bromide.
[0132] Examples of thiol compounds include 3-mercaptopropyltrimethoxysilane; 2-mercaptobenzoxazole; decanethiol; and thiobenzoic acid.
[0133] Among these polymerization accelerators, at least one selected from the group consisting of amines, thiourea compounds, vanadium compounds, and copper compounds is more preferably used, and among these, at least one selected from the group consisting of 1-(2-pyridyl)-2-thiourea, N,N-di(2-hydroxyethyl)-p-toluidine, ethyl 4-(N,N-dimethylamino)benzoate, 4,4-dimethylethylenethiourea, vanadyl acetylacetonate (IV), copper acetylacetonate, and copper acetate (II) is further preferably used as the polymerization accelerator.
[0134] The content of the polymerization accelerator in the dental filling and restoring material is not particularly limited, but from the viewpoint of the hardening property of the dental filling and restoring material, the content of the polymerization accelerator is preferably 0.001 to 30 parts by mass relative to 100 parts by mass of the total mass of the polymerizable monomer (C). By the content of the polymerization accelerator being 0.001 parts by mass or more, the polymerization can be sufficiently advanced and stickiness can be prevented. From this viewpoint, the content of the polymerization accelerator is more preferably 0.05 parts by mass or more, even more preferably 0.1 parts by mass or more, and even more preferably 0.3 parts by mass or more, relative to 100 parts by mass of the total mass of the polymerizable monomer (C). On the other hand, by the content of the polymerization accelerator being 30 parts by mass or less, the precipitation of the polymerization accelerator from the dental filling and restoring material can be prevented. From this viewpoint, the content of the polymerization accelerator is more preferably 20 parts by mass or less, even more preferably 10 parts by mass or less, and even more preferably 5.0 parts by mass or less, relative to 100 parts by mass of the total mass of the polymerizable monomer (C).
[0135] In addition, in the dental filling and restoring material, a chemical polymerization initiator and a polymerization accelerator may be combined to form a redox polymerization initiator. In this case, from the viewpoint of storage stability, the chemical polymerization initiator and the polymerization accelerator are preferably stored in separate containers. In this case, the dental filling and restoring material is preferably provided as a dental filling and restoring material characterized by being packaged at least in a first material containing a chemical polymerization initiator and a second material containing a polymerization accelerator. This makes it difficult for polymerization shrinkage to occur because polymerization proceeds at a low initiator concentration, and can suppress the gap between the tooth substance and the dental composite resin, which is a cause of secondary caries.
[0136] In addition, the dental filling and restoring material is more preferably provided as a kit in the form of a two-material type consisting of the first material and the second material. In this case, it is even more preferable that the dental filling and restoring material is provided as a kit in the form of a two-paste type, in which both the first material and the second material are paste-like. When the dental filling and restoring material is provided as a kit in the form of a two-paste type, the pastes are stored in a state in which they are isolated from each other, and the two pastes are kneaded together just before use to allow chemical polymerization to proceed. In addition, when the dental filling and restoring material further contains a photopolymerization initiator, it is preferable to proceed with photopolymerization in addition to chemical polymerization to harden the dental filling and restoring material. In one embodiment of the dental filling and restorative material packaged in the first and second materials, it is more preferable that the second material further contains the organic fluorinating agent (A), from the viewpoint of suppressing a decrease in the kick-off temperature of the peroxide (D) acting as a polymerization initiator and maintaining storage stability. In other words, from the viewpoint of storage stability, the dental filling and restorative material preferably comprises a first material containing a peroxide (D) and a second material not containing a peroxide (D), more preferably the second material contains an organic fluorinating agent (A), and further more preferably the first material does not contain an organic fluorinating agent (A).
[0137] In addition, in the dental filling and restoring material, a photopolymerization initiator may be used in combination with a polymerization accelerator such as an aldehyde, a thiol compound, or a triazine compound. In this case, by not containing a redox polymerization initiator, it can be provided as a dental filling and restoring material consisting of only one material. This eliminates the need for kneading in a two-material type product consisting of the first material and the second material, prevents loss of material due to kneading, and is preferable in terms of improving operability for users.
[0138] <Other glass> The dental filling and restoring material may contain glasses other than the ion-releasing glass (B) (hereinafter referred to as "other glasses"). Other glasses include, for example, lanthanum glass; borosilicate glass; soda glass; barium glass; strontium glass; glass ceramics; aluminosilicate glass; barium boroaluminosilicate glass; and strontium boroaluminosilicate glass. These may be used alone or in combination of two or more. The shape of the other glasses is not particularly limited, and they may be amorphous or spherical, and the particle size can be appropriately selected. The above other glasses may be surface-treated with a known surface treatment agent such as a silane coupling agent before use, if necessary, in order to adjust the miscibility with the polymerizable monomer (C). Examples of such surface treatment agents include vinyltrimethoxysilane, vinyltriethoxysilane, vinyltrichlorosilane, vinyltri(β-methoxyethoxy)silane, 3-methacryloyloxypropyltrimethoxysilane, 11-methacryloyloxyundecyltrimethoxysilane, 3-glycidoxypropyltrimethoxysilane, 3-mercaptopropyltrimethoxysilane, and 3-aminopropyltriethoxysilane.
[0139] The method of the surface treatment can be any known method without any particular limitation, and examples of such methods include a method in which the surface treatment agent is sprayed onto the other glass while vigorously stirring the other glass, a method in which the other glass and the surface treatment agent are dispersed or dissolved in a suitable solvent and then the solvent is removed, or a method in which the alkoxy groups of the surface treatment agent are hydrolyzed in an aqueous solution with an acid catalyst to convert them to silanol groups, which are then attached to the surface of the other glass in the aqueous solution and then the water is removed. In any of these methods, the reaction between the surface of the other glass and the surface treatment agent can be completed by heating at a temperature usually in the range of 50 to 150°C, thereby completing the surface treatment. When the dental filling and restoring material contains other glasses, the mass of the other glasses in the dental filling and restoring material is, from the viewpoint of adjusting the paste properties, preferably 1 to 60 parts by mass, more preferably 3 to 50 parts by mass, and even more preferably 5 to 45 parts by mass per 100 parts by mass of the ion-releasing glass (B) in the dental filling and restoring material.
[0140] <Filler> The dental filling and restoring material preferably further contains a filler in order to adjust the paste properties of the dental filling and restoring material before hardening, to impart X-ray contrast to the hardened material, or to further improve the strength of the hardened material, etc. Examples of fillers that can be used include organic fillers, inorganic fillers, and organic-inorganic composite fillers.
[0141] Examples of the organic filler material include polymethyl methacrylate, polyethyl methacrylate, methyl methacrylate-ethyl methacrylate copolymer, cross-linked polymethyl methacrylate, cross-linked polyethyl methacrylate, polyester, polyamide, polycarbonate, polyphenylene ether, polyoxymethylene, polyvinyl chloride, polystyrene, polyethylene, polypropylene, chloroprene rubber, nitrile rubber, ethylene-vinyl acetate copolymer, styrene-butadiene copolymer, acrylonitrile-styrene copolymer, and acrylonitrile-styrene-butadiene copolymer. These may be used alone or in combination of two or more. The shape of the organic filler is not particularly limited, and amorphous fillers and spherical fillers can be appropriately selected and used, and the particle size of the filler can be appropriately selected and used.
[0142] Examples of inorganic filler materials include quartz, silica, alumina, silica-titania, silica-titania-barium oxide, silica-zirconia, and silica-alumina. These may also be used alone or in combination of two or more. The shape of the inorganic filler is not particularly limited, and irregular fillers and spherical fillers can be appropriately selected and used, and the particle size of the filler can be appropriately selected and used.
[0143] The inorganic filler may be surface-treated with a known surface treatment agent such as a silane coupling agent before use, if necessary, in order to adjust the miscibility with the polymerizable monomer. Examples of such surface treatment agents include those similar to those described in "Other Glasses". The method of the surface treatment may also be the same as those described in "Other Glasses".
[0144] The organic-inorganic composite filler is obtained by adding a monomer compound to the inorganic filler described above in advance, forming a paste, polymerizing it, and pulverizing it. For example, TMPT filler (trimethylolpropane trimethacrylate and silica filler mixed, polymerized, and pulverized) can be used as the organic-inorganic composite filler. The shape of the organic-inorganic composite filler is not particularly limited, and amorphous fillers, spherical fillers, etc. can be appropriately selected and used, and the particle size of the filler can be appropriately selected and used.
[0145] The content of the filler is not particularly limited, but from the viewpoint of the handleability of the dental filling and restorative material and the strength of the cured product thereof, it is preferably 50 to 500 parts by mass, more preferably 60 to 400 parts by mass, even more preferably 65 to 300 parts by mass, and even more preferably 70 to 200 parts by mass, relative to 100 parts by mass of the total mass of the polymerizable monomer (C).
[0146] <Other ion-releasing compounds> The dental filling and restorative material may contain an ion-releasing compound other than the organic fluorinating agent (A) and the ion-releasing glass (B) (hereinafter referred to as "other ion-releasing compounds") for the purpose of imparting acid resistance to tooth structure. Examples of ion-releasing compounds include fluoride ion-releasing compounds, calcium ion-releasing compounds, zinc ion-releasing compounds, strontium ion-releasing compounds, phosphate ion-releasing compounds, borate ion-releasing compounds, etc. Among these, fluoride ion-releasing compounds, calcium ion-releasing compounds, and zinc ion-releasing compounds are preferably used because they have a large effect of imparting acid resistance to teeth, and fluoride ion-releasing compounds are more preferred. When the dental filling and restoring material contains the other ion-releasing compounds, the other ion-releasing compounds are preferably at least one selected from the group consisting of fluoride ion-releasing compounds, calcium ion-releasing compounds and zinc ion-releasing compounds, more preferably contain at least a fluoride ion-releasing compound, and even more preferably contain both at least one selected from the group consisting of calcium ion-releasing compounds and zinc ion-releasing compounds and a fluoride ion-releasing compound.
[0147] Examples of the fluorine ion releasing compound include lithium fluoride, sodium fluoride, potassium fluoride, rubidium fluoride, cesium fluoride, beryllium fluoride, magnesium fluoride, calcium fluoride, strontium fluoride, barium fluoride, aluminum fluoride, manganese (II) fluoride, iron (II) fluoride, iron (III) fluoride, cobalt (II) fluoride, copper (II) fluoride, zinc fluoride, antimony (III) fluoride, lead (II) fluoride, silver (I) fluoride, cadmium fluoride, tin (II) fluoride, tin (IV) fluoride, diammine silver fluoride, titanium fluoride, ammonium hexafluorotitanate, sodium hydrogen fluoride, and potassium hydrogen fluoride. Examples of the fluoride salt include metal fluoride salts such as ammonium, sodium fluorophosphate, potassium hexafluorotitanate, sodium hexafluorosilicate, sodium hexafluorophosphate, sodium hexafluorotin(IV), hexafluorostannate(IV) alanine, sodium pentafluorodistannate(II), and potassium hexafluorozirconate; fluoride ion-releasing ammonium salts such as ammonium hydrofluoride and cetylamine hydrofluoride; phosphate salts such as sodium monofluorophosphate; hydrate salts thereof; and fluoride ion-releasing polymers such as copolymers of (meth)acrylic acid esters and (meth)acrylic acid fluoride. These may be used alone or in combination of two or more.
[0148] Among these, from the viewpoints of excellent solubility and ease of forming an acid-resistant layer, the fluorine ion-releasing compound is preferably sodium fluoride, sodium fluorophosphate, strontium fluoride, zinc fluoride, titanium fluoride, ammonium hexafluorotitanate, or a hydrate salt thereof, and more preferably sodium fluoride, zinc fluoride, titanium fluoride, ammonium hexafluorotitanate, or a hydrate salt thereof.
[0149] Examples of the calcium ion releasing compound include phosphorus-containing calcium salts such as tetracalcium phosphate, anhydrous calcium monohydrogen phosphate, tricalcium phosphate, anhydrous calcium dihydrogen phosphate, amorphous calcium phosphate, acidic calcium pyrophosphate, calcium monohydrogen phosphate dihydrate, and calcium dihydrogen phosphate monohydrate; phosphorus-free calcium salts such as calcium hydroxide, calcium oxide, calcium chloride, calcium nitrate, calcium acetate, calcium lactate, calcium citrate, calcium metasilicate, dicalcium silicate, tricalcium silicate, and calcium carbonate; unsaturated acid metal salt monomers such as calcium (meth)acrylate; and hydrate salts thereof. These may be used alone or in combination of two or more.
[0150] Among these, as calcium ion-releasing compounds, from the viewpoints of excellent ion-releasing properties and ease of strengthening tooth structure, preferred are tetracalcium phosphate, anhydrous calcium monohydrogen phosphate, tricalcium phosphate, anhydrous calcium dihydrogen phosphate, amorphous calcium phosphate, calcium hydroxide, calcium oxide, calcium metasilicate, dicalcium silicate, tricalcium silicate, and calcium (meth)acrylate, and more preferred are tetracalcium phosphate, anhydrous calcium monohydrogen phosphate, anhydrous calcium dihydrogen phosphate, amorphous calcium phosphate, and calcium (meth)acrylate.
[0151] Examples of the zinc ion-releasing compound include zinc halide salts such as zinc fluoride, zinc chloride, zinc bromide, and zinc iodide; zinc salts with organic acids such as zinc acetate, zinc citrate, zinc gluconate, zinc naphthenate, and zinc stearate; unsaturated acid metal salt monomers such as zinc (meth)acrylate; and hydrate salts thereof.
[0152] Among these, as zinc ion-releasing compounds, from the viewpoint of excellent ion-releasing properties and ease of strengthening tooth structure, zinc fluoride, zinc chloride, zinc acetate, zinc gluconate, zinc (meth)acrylate, and hydrates thereof are preferred, with zinc fluoride, zinc chloride, zinc (meth)acrylate, and hydrates thereof being more preferred.
[0153] The shape of the other ion-releasing compound is not particularly limited, and may be any particle shape such as spherical, needle-like, plate-like, crushed, or scaly. It may also be dissolved in a polymerizable monomer. When the other ion-releasing compound is particulate, the average primary particle size is preferably 0.001 to 10 μm, more preferably 0.005 to 5.0 μm, even more preferably 0.01 to 4.0 μm, and even more preferably 0.05 to 1.0 μm, from the viewpoints of the handleability of the dental filling and restorative material and the ion release property, mechanical strength, and transparency of the cured product. In this specification, the average primary particle size of the other ion-releasing compound can be determined by observation with an optical microscope or an electron microscope. Specifically, optical microscope observation is convenient for measuring the particle size of particles with a particle size of 100 nm or more, and electron microscope observation is convenient for measuring the particle size of particles with a particle size of less than 100 nm.
[0154] The mass of the other ion-releasing compound in the dental filling and restorative material is not particularly limited, but from the viewpoint of the handleability of the obtained dental filling and restorative material and the ion-releasing property of the cured product, it is preferably 1.0 to 400 parts by mass, more preferably 10 to 300 parts by mass, and even more preferably 20 to 200 parts by mass, relative to 100 parts by mass of the total mass of the polymerizable monomer (C).
[0155] <Additives> In addition, the dental filling and restorative material may contain other known additives as necessary within the range in which the effects of the present invention are achieved. Examples of other additives include polymerization inhibitors, antioxidants, pigments, dyes, ultraviolet absorbers, organic solvents, thickeners, etc., other than the above-mentioned components.
[0156] Examples of the polymerization inhibitor include hydroquinone, hydroquinone monomethyl ether, dibutyl hydroquinone, dibutyl hydroquinone monomethyl ether, t-butyl catechol, 2-t-butyl-4,6-dimethylphenol, 2,6-di-t-butylphenol, and 3,5-di-t-butyl-4-hydroxytoluene. When the dental filling and restorative material contains a polymerization inhibitor, the content of the polymerization inhibitor is preferably 0.001 to 1.0 part by mass, more preferably 0.005 to 0.5 part by mass, and even more preferably 0.01 to 0.1 part by mass, based on 100 parts by mass of the total mass of the polymerizable monomer (C).
[0157] In addition, the total mass of the other additives in the dental filling and restoring material is not particularly limited as long as the effects of the present invention are achieved, but from the viewpoint of making the effects of the present invention easier to achieve, the total mass of the other additives in the dental filling and restoring material is preferably 20% by mass or less, more preferably 15% by mass or less, even more preferably 10% by mass or less, still more preferably 5% by mass or less, and still more preferably 2% by mass or less, and 0% by mass or more, in 100% by mass of the dental filling and restoring material. In other words, the mass of the other additives in the dental filling and restoring material is preferably 0 to 20% by mass in 100% by mass of the dental filling and restoring material.
[0158] Moreover, from the viewpoint of easily preventing a decrease in strength and water resistance of the cured product, and clouding, etc., it is preferable that the dental filling and restoring material does not substantially contain polycarboxylic acid. Note that, "substantially does not contain polycarboxylic acid" means that the mass of polycarboxylic acid is 5.0 mass% or less, preferably 1.0 mass% or less, more preferably 0.5 mass% or less, even more preferably 0.1 mass% or less, and still more preferably 0.05 mass% or less, in 100 mass% of the dental filling and restoring material. Furthermore, as described above, from the viewpoint of improving the strength and color tone of the obtained cured product, it is preferable that the dental filling and restoring material does not contain a solvent such as water, ethanol, acetone, etc., or that the content of the solvent is more than 0 parts by mass and not more than 1.0 parts by mass per 100 parts by mass of the total mass of the dental filling and restoring material.
[0159] The dental filling and restorative material can be produced by any method known to those skilled in the art without any particular limitation on the method of mixing the components.
[0160] Furthermore, the dental filling and restoring material can be used in combination with a tooth surface treatment material or a dental adhesive, as described below, for example, with a tooth surface treatment material or a dental adhesive containing a part of a redox initiator. When the dental filling and restoring material is used in combination with a tooth surface treatment material or a dental adhesive containing a part of a redox initiator, redox polymerization is initiated from the interface between the tooth substance and the dental filling and restoring material, so that the gap and the invasion of bacteria at the interface between the tooth substance and the dental filling and restoring material are suppressed.
[0161] <Physical properties of dental filling and restorative materials> (Tooth dissolution inhibition) The hardened material of the dental filling and restoring material preferably has a high tooth structure strengthening ability, and particularly preferably has a high tooth structure dissolution inhibiting ability. Specifically, the hardened material of the dental filling and restoring material is filled into a class I cavity provided in a bovine mandibular anterior tooth to prepare an evaluation sample, and the sample is immersed in an acetate buffer of a predetermined concentration at a predetermined temperature for a predetermined time, and then a calcium ion concentration CR is measured. The amount of inhibition of tooth structure dissolution calculated as a ratio of the difference between the calcium ion concentration CL measured in the same manner for a bovine mandibular anterior tooth without a cavity (CL-CR) is preferably 50 to 99%, more preferably 53 to 99%, and even more preferably 55 to 99%. The amount of inhibition of dentin dissolution is measured in detail by the method described in the Examples below. The dentin dissolution inhibiting amount is set within the above range by, for example, selecting and adjusting either the type and amount of the organic fluorinating agent (A) or the type and amount of the ion-releasing glass (B).
[0162] (Bending strength) The hardened material of the dental filling and restoring material preferably has a high bending strength from the viewpoint of preventing fracture during occlusion. The bending strength of the dental filling and restoring material is preferably 80 MPa or more, more preferably 85 MPa or more, even more preferably 90 MPa or more, even more preferably 95 MPa or more, and even more preferably 100 MPa or more, as measured in accordance with JIS T6514 2015. There is no particular upper limit, but from the viewpoint of ease of manufacture, it is, for example, 200 MPa or less. In other words, the bending strength of the hardened material of the dental filling and restoring material is preferably 80 to 200 MPa. The bending strength can be set within the above range by, for example, selecting or adjusting any one of the type and amount of the organic fluorinating agent (A), the type and amount of the ion-releasing glass (B), and the type and amount of the polymerizable monomer (C).
[0163] (Aesthetics) The hardened product of the dental filling and restoring material preferably has high aesthetics. Specifically, the transparency ΔL of a sample of the hardened product formed to a size of φ10 mm×1.0 mm, measured by a spectrophotometer, is preferably 25 or more, more preferably 26 or more, even more preferably 28 or more, and even more preferably 30 or more. There is no particular upper limit, but from the viewpoint of ease of production, it is, for example, 40 or less. In other words, the transparency ΔL of the hardened product of the dental filling and restoring material is preferably 25 to 40. The transparency ΔL is measured in detail by the method described in the Examples section below. In addition, the transparency ΔL and aesthetics can be set within the above range by, for example, selecting and adjusting either the type and blending amount of the organic fluorinating agent (A) or the type and blending amount of the ion-releasing glass (B).
[0164] (Polymerization shrinkage stress) The dental filling and restoring material preferably has a small polymerization shrinkage stress from the viewpoint of preventing detachment from tooth structure. More specifically, the polymerization shrinkage stress measured by a universal testing machine when filling the dental filling and restoring material into a ring-shaped mold with an inner diameter of 5.5 mm and a thickness of 0.8 mm and curing it by irradiating light is preferably 9.0 MPa or less, more preferably 8.0 MPa or less, even more preferably 7.0 MPa or less, even more preferably 6.6 MPa or less, even more preferably 6.0 MPa or less, and particularly preferably 5.0 MPa or less. There is no particular limit to the lower limit, but from the viewpoint of ease of production, it is, for example, 3.5 MPa or more. In other words, the polymerization shrinkage stress of the dental filling and restoring material is preferably 3.5 to 9.0 MPa. The polymerization shrinkage stress is measured in detail by the method described in the Examples section below. The polymerization shrinkage stress can be set within the above range by, for example, selecting or adjusting any one of the type and amount of the organic fluorinating agent (A), the type and amount of the ion-releasing glass (B), and the type and amount of the polymerizable monomer (C).
[0165] (Fluoride ion releasing) The hardened material of the dental filling and restorative material preferably has a suitable fluoride ion releasing property in order to easily secure the necessary tooth substance strengthening ability. More specifically, when a hardened material formed in a size of 15 mm in diameter and 1 mm in thickness is immersed in a phosphate buffer solution of a predetermined concentration at a predetermined temperature for a predetermined period of time, the amount of fluoride ions dissolved in the phosphate buffer solution is preferably 10 μg / g / day or more, more preferably 12 μg / g / day or more, and even more preferably 14 μg / g / day or more. In addition, the amount of fluoride ions is 35 μg / g / day or less, more preferably 32 μg / g / day or less, and even more preferably 30 μg / g / day or less in order to easily secure aesthetics and strength. In other words, the amount of fluoride ions is preferably 10 to 35 μg / g / day. The amount of released fluoride ions is measured in detail by the method described in the Examples below. The amount of fluoride ions released can be set within the above range by, for example, selecting and adjusting either the type and amount of the organic fluorinating agent (A) or the type and amount of the ion-releasing glass (B).
[0166] (Bactericidal) The hardened material of the dental filling and restoring material may have bactericidal properties from the viewpoint of easily suppressing the progression of caries. More specifically, the hardened material is subjected to an antibacterial test based on JIS Z 2801 2000, and when the number of live bacteria of the hardened material is Y and the number of live bacteria of a polyethylene film (standard sample) is X, the hardened material is judged to have bactericidal properties if the antibacterial activity value expressed as the common logarithm of X / Y is 2.0 or more. The antibacterial activity value is more preferably 2.1 or more, more preferably 2.3 or more, and even more preferably 2.5 or more. There is no particular upper limit, but from the viewpoint of biological safety, it is, for example, 3.5 or less. In other words, the antibacterial activity value is preferably 2.0 to 3.5. The antibacterial activity value is measured in detail by the method described in the Examples below. The antibacterial activity value can be set within the above range by, for example, selecting and adjusting either the type and amount of the organic fluorinating agent (A) or the type and amount of the ion-releasing glass (B).
[0167] [kit] A first kit according to an embodiment of the present invention is a kit including the above-mentioned dental filling and restorative material and a tooth surface treatment material. The tooth surface treatment material is not particularly limited, and may be, for example, a two-liquid tooth surface treatment material consisting of a first liquid containing a silver compound and a second liquid containing an alkali metal halide or an alkaline earth metal halide, or a one-liquid tooth surface treatment material containing silver ions, iodide ions, and water. From the viewpoint of ease of handling, a one-liquid tooth surface treatment material is preferable. Particularly preferred one-liquid tooth surface treatment materials include the tooth surface treatment material described in JP 2021-107371 A and the tooth surface treatment material described in WO 2018 / 092889 A. An example of a commercially available tooth surface treatment material is "PANAVIA (registered trademark) V5 Tooth Primer" manufactured by Kuraray Noritake Dental Co., Ltd.
[0168] A second kit according to an embodiment of the present invention is a kit including the above-mentioned dental filling and restorative material and a dental adhesive. The dental adhesive is not particularly limited, and various dental adhesives known as dental bonding materials can be used. The dental adhesive is usually an adhesive composition containing an acidic component and water, and further contains a polymerizable monomer, a polymerization initiator, a solvent, and other compounding agents as necessary. Particularly preferred dental adhesives include dental bonding materials containing an acidic group-containing (meth)acrylic polymerizable monomer, a water-soluble polymerizable monomer, and a polymerization initiator, as described in International Publication No. 2013 / 145621 and International Publication No. 2015 / 190099. The dental adhesive may be a one-material type that can be used as it is, or a two-material type that is divided into materials A and B and mixed together just before use. An example of a commercially available dental adhesive is the dental bonding material "Clearfil (registered trademark) Universal Bond QuickER" manufactured by Kuraray Noritake Dental Co., Ltd.
[0169] The first and second kits may further include a third material other than the dental filling and restorative material, the tooth surface treatment material, and the dental adhesive, such as a finishing material, a fissure sealant, and a dentin hypersensitivity suppressant. EXAMPLES
[0170] The present invention will now be described in more detail with reference to examples, but the present invention is not limited to these examples in any way.
[0171] Each component used in the examples and comparative examples will be explained below together with its abbreviation.
[0172] [Organic fluorinating agent (A)] <Electrophilic fluorinating agent (A-2)> "F-TEDA-BF4": N-fluoro-N'-(chloromethyl)triethylenediaminebis(tetrafluoroborate) "FPTS": 1-fluoropyridinium trifluoromethanesulfonate "FTP-BF4": 1-fluoro-2,4,6-trimethylpyridinium tetrafluoroborate "FDBI": 1-fluoro-3,3-dimethyl-1,2-benzoiodoxol <Nucleophilic fluorinating agent (A-1)> "TBAF": Tetrabutylammonium fluoride "Morph-DAST": Morpholinosulfur trifluoride
[0173] [Fluorine compounds] "TBA-BF4": Tetrabutylammonium tetrafluoroborate "TBA-PF6": Tetrabutylammonium hexafluorophosphate "EP y T": 1-Ethylpyridinium tetrafluoroborate "BMP y B": 1-butyl-3-methylpyridinium bis(trifluoromethylsulfonyl)imide "NNT": N-methyl-N-[(trifluoromethyl)thio]-p-toluenesulfonamide "TFP y ": 2,3,5-trifluoropyridine
[0174] [Ion-releasing glass (B)] "G018-090": Silane-treated fluoroaluminosilicate glass manufactured by Schott, average particle size: 0.7 μm "G018-117": Silane-treated barium fluoroaluminosilicate glass powder manufactured by Schott, average particle size: 2 μm, silane treatment concentration: 1.4% [Other glass] "S8235": Silane-treated barium glass powder manufactured by Schott, average particle size: 2μm, silane treatment concentration: 1.4%
[0175] [Polymerizable monomer (C)] <(Meth)acrylic compound (c-1)> "UDMA": 2,2,4-trimethylhexamethylenebis(2-carbamoyloxyethyl)dimethacrylate (Kyoeisha Chemical Co., Ltd.) "#801": 1,2-bis(3-methacryloxy-2-hydroxypropoxy)ethane <Polymerizable monomers other than (meth)acrylic compounds (c-1)> 3G: Triethylene glycol dimethacrylate "POB-MA": m-phenoxybenzyl methacrylate (Kyoeisha Chemical Co., Ltd.) "DD": 1,10-decanediol dimethacrylate
[0176] [Photopolymerization initiator] "CQ": Camphorquinone "BAPO": Bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide [Chemical polymerization initiator] <Peroxide (D)> "THP": 1,1,3,3-tetramethylbutyl hydroperoxide "BPO": Benzoyl peroxide [Polymerization accelerator] "PDE": Ethyl 4-(N,N-dimethylamino)benzoate "NMDEA": N-methyldiethanolamine "pyTU": 1-(2-pyridyl)-2-thiourea "DMETU": 4,4-Dimethylethylenethiourea "VOAA": Vanadyl acetylacetonate "CuOA": Copper(II) acetate "OBA": pn-Octyloxybenzaldehyde
[0177] [Antioxidants] "BHT": 3,5-di-t-butyl-4-hydroxytoluene
[0178] [Examples 1 to 15 and Comparative Examples 1 to 8] Among the components shown in Tables 1 to 5 below, the components in the masses shown in the "monomer composition" column were mixed at room temperature (25°C), and the entire components were treated as "monomers" and further ion-releasing glass (B) and other glasses were added at the mass ratios shown in the "paste composition" column of Tables 1 to 5. The 1-material and 2-material dental filling and restorative materials in Examples 1 to 8 and Comparative Examples 1 to 8 and Examples 9 to 11 were prepared by mixing them at room temperature (25°C). All of these were in a paste form and had a fluidity suitable for filling and applying to teeth. Hereinafter, the 2-material dental filling and restorative materials (Examples 1 to 8 and Comparative Examples 1 to 8) are also referred to as "2-material pastes", and the 1-material dental filling and restorative materials (Examples 9 to 11) are also referred to as "1-material pastes". For the two-material paste of the dental filling and restorative materials of each Example and Comparative Example, the first and second material pastes were prepared as described above, and then filled into a polyolefin resin container (total volume 5 mL, manufactured by Mixpack, product code "SDL 005-01-SI") in which a pair of identical cylinders were arranged in parallel. A mixer was attached to the front end of the container, and an extrusion device (manufactured by Mixpack, product code "PED 005-01-SI") consisting of a pair of cylindrical extrusion members connected and fixed to the rear end was attached to form a kneading device. By pushing the extrusion members, an equal volume of paste was collected from inside the cylindrical container. A mixing tip (manufactured by Mixpack, product code "ML 2.5-08-S") having eight stirring blades (elements) was used as the mixer. Among the dental filling and restorative materials of each Example and Comparative Example, the one-material paste was prepared as described above, and then filled into a container of "Clearfill Majesty LV (manufactured by Kuraray Noritake Dental Co., Ltd., cylindrical length 7.5 cm, inner diameter of opening 0.8 cm. "Clearfill" and "Majesty" are both registered trademarks.)". A guide tip with a length of 1.5 cm and an inner diameter of 0.8 mm was attached to the tip of the container before use. The fluoride ion release, dentin dissolution inhibition rate, bactericidal activity, bending strength, aesthetics, polymerization shrinkage stress, and storage stability of the obtained dental filling and restorative material were measured or evaluated as follows.
[0179] <Fluoride ion release> Each dental filling and restorative material (in the case of one-material type) or its kneaded product (in the case of two-material type) of the examples and comparative examples was loaded into a mold with a diameter of 15 mm and a thickness of 1 mm, and then left to stand in a thermostatic chamber at 37°C for 1 hour to harden, after which the hardened material was removed from the mold and immersed in 4 ml of 0.2 M phosphate buffer (pH 7, 37°C). After immersion for 28 days, 2 mL of total ionic strength adjustment buffer (TISAB solution) was added, and the amount of fluoride ions dissolved in the phosphate buffer was quantified using a fluoride ion electrode (manufactured by Thermo Fisher Scientific). In this test, if the concentration is 10 μg / g / day or more, an acid-resistant layer tends to be formed, and it is judged that the fluoride ion release required to obtain sufficient tooth structure strengthening ability is ensured.
[0180] <Tooth dissolution inhibition rate> The labial surface of a bovine mandibular anterior tooth was polished with #80 silicon carbide paper (Nihon Kenshi Co., Ltd.) under running water to obtain a sample with the flat surface of the enamel exposed. The obtained sample was further polished with #1000 silicon carbide paper (Nihon Kenshi Co., Ltd.) under running water. After polishing, the water on the surface was dried by air blowing. The sample was cut along the tooth axis, and a piece of adhesive tape with a thickness of approximately 150 μm and a square hole of 2 mm in width and length was attached to the smooth surface of one of the samples (sample L) after drying to define the demineralized area. A class I cavity of 2 mm in width, 2 mm in length, and 1 mm in depth was formed in the other sample (sample R). For the two-material paste of the dental filling and restorative materials of each Example and Comparative Example, a tooth surface treatment material (Panavia (registered trademark) V5 Tooth Primer, manufactured by Kuraray Noritake Dental Co., Ltd.) was applied to the Class I cavity of Sample R, and the cavity was left to stand for 20 seconds, followed by air blowing. The dental filling and restorative material was then filled. For the one-material paste of the dental filling and restorative materials of each Example and Comparative Example, a dental adhesive (Clearfil (registered trademark) Universal Bond QuickER, manufactured by Kuraray Noritake Dental Co., Ltd.) was applied to the Class I cavity of Sample R, and adhesion treatment was performed according to the method recommended by the manufacturer and described in the attached document of the product. Then, the dental filling and restorative material was filled. The dental filling material was cured by irradiating it with light for 10 seconds using a dental LED light irradiator (product name "Pencure 2000", manufactured by Morita Co., Ltd.) The obtained sample was polished with #1000 silicon carbide paper (manufactured by Nihon Kenshi Co., Ltd.) under dry conditions to make the surface smooth. A piece of adhesive tape with a thickness of about 150 μm and a square hole with a width of 4 mm and a length of 2 mm was applied to the tooth so that the entire cavity was exposed through the square hole. Sample L and Sample R were placed in separate containers, and 4 mL of Dulbecco's Phosphate-Buffered Saline (DPBS) was added to each sample, and the samples were left to stand at 37°C for 24 hours. After standing, the samples were washed with water, and 4 mL of 0.5 M acetate buffer was added to each sample, and the samples were left to stand at 37°C for 24 hours. After standing, the acetate buffer was collected. The calcium ion concentration in the acetate buffer was measured using a compact calcium ion meter (LAQUAtwin CA-11, manufactured by Horiba Advanced Techno Co., Ltd.). The dentin dissolution inhibition rate R was calculated based on the following formula (1) and used as an index of dentin strengthening ability. R=[(CL-CR) / CL]×100[%]...Equation (1) CL: calcium ion concentration of sample L CR: Calcium ion concentration of sample R
[0181] <Bactericidal property> The dental filling and restorative materials prepared in each of the Examples and Comparative Examples were subjected to an antibacterial test based on JIS Z 2801 2000. Specifically, a bacterial solution containing Escherichia coli and a bacterial solution containing Staphylococcus aureus were dropped onto each of the cured products, and the number of live bacteria was counted after 24 hours (n=3). The same procedure was performed on a polyethylene film (standard sample), and the number of live bacteria was counted (n=3). When the number of live bacteria in the standard sample is X and the number of live bacteria in the samples of the Examples and Comparative Examples is Y, the common logarithm of X / Y was used as the antibacterial activity value. If the antibacterial activity value was 2.0 or more, it was evaluated as "bactericidal", and if the antibacterial activity value was less than 2.0, it was evaluated as "not bactericidal". In the following Tables 1 to 5, the former is indicated by "+" and the latter is indicated by "-".
[0182] <Bending strength> The evaluation was performed by a bending test in accordance with JIS T6514 2015. That is, for each example and comparative example, the dental filling and restoring material (in the case of one-material type) or its kneaded product (in the case of two-material type) was filled into a SUS mold (having a rectangular parallelepiped space of 2 mm high x 2 mm wide x 25 mm long, with both ends in the width direction forming two planes (upper and lower surfaces) perpendicular to the width direction, and the space is exposed on the upper and lower surfaces), and the upper and lower surfaces were pressed with slide glass. The material was cured by irradiating light to both sides from the upper and lower surfaces (2 mm x 25 mm surface and the opposite 2 mm x 25 mm surface) for 10 seconds at one point, with light irradiated to both sides for 10 seconds at one point. For each of the obtained cured products, a bending test was carried out at a crosshead speed of 2 mm / min using a universal testing machine (manufactured by Shimadzu Corporation, "Autograph (registered trademark) AG-I 100 kN") to measure the bending strength.
[0183] <Aesthetics> For each Example and Comparative Example, the prepared dental filling and restorative material (in the case of one-material type) or its kneaded product (in the case of two-material type) was filled into a SUS mold (hole of φ10 mm×1.0 mm), and the top and bottom were pressed with slide glass. The material was cured by irradiating both sides with light for 10 seconds at each point, 9 points on each side, using a dental polymerization LED light irradiator (product name "Pencure 2000", manufactured by Morita Corporation). Each of the obtained cured materials was immersed in 37°C water for one week, washed with water, and dried by air blowing. The transparency ΔL of the cured product after the above water immersion treatment was evaluated using a spectrophotometer (SE6000, manufactured by Nippon Denshoku Industries Co., Ltd., light source: D65 / 2, measurement window: φ6 mm). * a * b * Lightness in color space (L * / w), and L with a black board placed behind the hardened board * a * b * Lightness in color space (L * The transparency ΔL was calculated based on the following formula (2) and used as an index of aesthetics. ΔL = (L * / w)-(L * / b)...Formula (2)
[0184] <Polymerization shrinkage stress> A ring-shaped mold (made of stainless steel, inner diameter 5.5 mm x thickness 0.8 mm) placed on a glass plate with a thickness of 4.0 mm was filled with the dental filling and restoring material (in the case of one-material type) or its kneaded product (in the case of two-material type) obtained in each Example or Comparative Example. The above glass plate was used after sandblasting with alumina powder having a particle size of 50 μm. Then, a stainless steel jig (φ5 mm) connected to a shrinkage stress measuring device (manufactured by Shimadzu Corporation, product name "MICRO STRAIN TESTER MST-I") was placed on the filled paste, and the dental filling and restoring material or its kneaded product was sandwiched and left to stand for 90 seconds, and then the paste was irradiated with light through the glass plate for 20 seconds using a dental polymerization LED light irradiator (product name "Pencure 2000", manufactured by Morita Corporation) to harden the paste. At this time, the polymerization shrinkage stress accompanying the hardening due to the polymerization reaction of the dental filling and restoring material proceeding by chemical polymerization for 90 seconds and light irradiation was measured by the universal testing machine (n=3).
[0185] <Storage stability> For each of the Examples and Comparative Examples, the hardening time of the prepared dental filling and restorative material (in the case of one-material type) or its kneaded product (in the case of two-material type) was measured. For the two-component paste, the hardening time was measured in accordance with JIS T6514 2015. For the one-component paste, the paste was extruded into the sample filling section for measuring the curing time, and then a glass plate was placed on top of it. Next, the paste was irradiated with light through the glass plate for 20 seconds using a dental polymerization LED light irradiator (product name "PenCure 2000", manufactured by Morita Corporation). The curing time was measured in accordance with JIS T6514 2015, except that the measurement start point was the start point of the light irradiation. Separately, the dental filling and restorative materials were left to stand at 60°C for two weeks. At this time, the two-material paste was left to stand in the container before the two materials were mixed, and the one-material paste was also left to stand in the container. After that, the temperature was returned to room temperature, and the setting time was measured in the same manner as above. The change in setting time was used as an index of storage stability, and was evaluated according to the following criteria, with "++" and "+" being considered as passing. · "++": The change in curing time is within 1 minute. · "+": The change in curing time is between 1 minute and 4 minutes. -: The change in curing time is 4 minutes or more.
[0186] The measurement and evaluation results of the dental filling and restorative materials of the examples and comparative examples are shown in Tables 1 to 6 below, together with their compositions. In Tables 1 to 6, "-" in the "Monomer composition" and "Paste composition" columns means that the corresponding component was not blended. In addition, "N / A" in the "Fluoride ion release amount" column means that the measurement was not performed. In addition, "E" in the "Dentin dissolution inhibition rate" column means that the dentin dissolution inhibition rate was 50% or less.
[0187] [Table 1] [Table 2] [Table 3] [Table 4] [Table 5] [Table 6]
[0188] As shown in Tables 1 to 6, the dental filling and restorative materials of Examples 1 to 15, which contain an organic fluorinating agent (A), an ion-releasing glass (B), and a polymerizable monomer (C), have cured products that have a moderately high fluoride ion release amount and a high dentin dissolution inhibition rate, compared to the dental filling and restorative materials of Comparative Examples 1 to 8, which do not contain either the organic fluorinating agent (A) or the ion-releasing glass (B). It is therefore clear that a cured product with good dentin strengthening ability can be obtained. It is also found that the hardened products of the dental filling and restoring materials of Examples 1 to 15 have high bending strength and excellent aesthetics. In particular, it is found that the hardened products of the dental filling and restoring materials of Examples 1 to 5, 7 to 12, 14, and 15 have high levels of dentin dissolution inhibition rate, bending strength, and aesthetics. Moreover, it is understood that all of the dental filling and restoring materials of Examples 1 to 15 are excellent in storage stability, and the dental filling and restoring materials of Examples 1 to 8 and 12 to 15 are low in polymerization shrinkage stress. It is also apparent that the hardened dental filling and restorative materials of Examples 1 to 5, 7 to 9, 12, 13 and 15 further have bactericidal properties. Furthermore, as is clear from a comparison between Example 1 or Example 5 and Example 7, for example, it can be understood that the hardened dental filling and restorative material using the electrophilic fluorinating agent (A-2) can significantly reduce the amount of organic fluorinating agent (A) used while ensuring a predetermined amount of fluoride ion release and inhibition of tooth dissolution (in other words, while ensuring a certain degree of tooth strengthening ability) compared to the hardened dental filling and restorative material using the nucleophilic fluorinating agent (A-1). Furthermore, as is clear from a comparison between Example 1 and Example 15, it can be seen that the hardened dental filling and restorative material using an electrophilic fluorinating agent (A-2) can achieve a significantly higher inhibition rate of dentin dissolution while ensuring a predetermined amount of fluoride ion release when using the same amount of organic fluorinating agent (A) compared to the hardened dental filling and restorative material using a nucleophilic fluorinating agent (A-1).
[0189] On the other hand, as shown in Tables 5 and 6, the hardened products of the dental filling and restoring materials of Comparative Examples 1, 2, and 4 to 8 that do not contain the organic fluorinating agent (A), and the hardened product of the dental filling and restoring material of Comparative Example 3 that does not contain the ion-releasing glass (B), generally had low values for the amount of fluoride ion released or the dentin dissolution inhibition rate, and it is clear that the dentin strengthening ability is significantly lower than that of the Examples. For example, as is clear from a comparison between Comparative Example 5 and Example 6, even if the same mass of a fluorine compound different from the organic fluorinating agent (A) is used instead of the organic fluorinating agent (A), a sufficient dentin dissolution inhibition rate is not obtained. And, as is clear from a comparison between Comparative Example 5 and Comparative Examples 6 to 8, even if the type or amount of the fluorine compound is changed, a sufficient dentin dissolution inhibition property is not obtained. [Industrial Applicability]
[0190] The dental filling and restoring material of the present invention can be used for restoring any tooth, and since the cured product has good aesthetics, it is preferably used for restoring, for example, incisors and canines. In addition, since the cured product of the dental filling and restoring material has high strength, it is preferably used for restoring cavities formed in molars. The dental filling and restoring material is used in the same manner as the conventionally known composite resin filling material is generally used.
Claims
1. A dental filling and restorative material comprising an organic fluorinating agent (A), an ion-releasing glass (B), and a polymerizable monomer (C).
2. The dental filling and restoring material according to claim 1, which does not contain a solvent or further contains a solvent, the mass of the solvent being greater than 0 parts by mass and not greater than 1.0 parts by mass per 100 parts by mass of the total mass of the dental filling and restoring material.
3. 3. The dental filling and restorative material according to claim 1, wherein the organic fluorinating agent (A) contains at least one element selected from the group consisting of nitrogen, phosphorus, boron, sulfur, and iodine.
4. The organic fluorinating agent (A) is selected from the group consisting of tetramethylammonium fluoride, tetraethylammonium fluoride, tetrabutylammonium fluoride, tetrabutylammonium difluorotriphenyltin, tetrabutylammonium difluorotriphenylsilicate, pyrimidine-2-sulfonyl fluoride, pyridine-2-sulfonyl fluoride, 2-chloro-1,3-bis(2,6-diisopropylphenyl)-1H-imidazolium chloride-cesium fluoride, perfluoro-1-butanesulfonyl fluoride, morpholinosulfur trifluoride, hexafluoropropene diethylamine, and 2-fluoro-1-methylpyridinium.
3. The dental filling and restorative material according to claim 1, which is at least one compound selected from the group consisting of p-toluenesulfonate; (diethylamino)sulfur trifluoride; 4-tert-butyl-2,6-dimethylphenylsulfur trifluoride; bis(2-methoxyethyl)aminosulfur trifluoride; 1,3-bis(2,6-diisopropylphenyl)-2-fluoroimidazolium tetrafluoroborate; 1-fluoropyridinium trifluoromethanesulfonate; 1,1'-difluoro-2,2'-bipyridinium bis(tetrafluoroborate); 1-fluoro-2,4,6-trimethylpyridinium tetrafluoroborate; 1-fluoro-3,3-dimethyl-1,2-benzoiodoxole; N-fluoro-N'-(chloromethyl)triethylenediamine bis(tetrafluoroborate); N-fluorobenzenesulfonimide; and salts thereof.
5. The dental filling and restoring material according to claim 1 or 2, wherein the polymerizable monomer (C) comprises a (meth)acrylic compound (c-1) having at least one group or bond selected from the group consisting of a hydroxyl group, a carboxylic acid group, an amino group, an amide group, and a urethane bond.
6. The dental filling and restoring material according to claim 5, wherein the mass of the organic fluorinating agent (A) is 0.005 to 30 parts by mass per 100 parts by mass of the (meth)acrylic compound (c-1).
7. 3. The dental filling and restoring material according to claim 1, wherein the mass of the organic fluorinating agent (A) is 0.1 to 10 parts by mass per 100 parts by mass of the total mass of the polymerizable monomer (C).
8. 3. The dental filling and restoring material according to claim 1, wherein the mass of the organic fluorinating agent (A) is 0.001 to 10 parts by mass per 100 parts by mass of the ion-releasing glass (B).
9. 3. The dental filling and restorative material according to claim 1, wherein the organic fluorinating agent (A) is an electrophilic fluorinating agent (A-2).
10. 3. The dental filling and restorative material according to claim 1, wherein the organic fluorinating agent (A) is a compound containing a quaternary ammonium ion.
11. 3. The dental filling and restorative material according to claim 1, wherein the organic fluorinating agent (A) is a hypervalent iodine compound.
12. 3. The dental filling and restorative material according to claim 1, wherein the ion-releasing glass (B) is at least one glass selected from the group consisting of soda-lime silicate glass, aluminosilicate glass, borosilicate glass, aluminoborosilicate glass, and fluoroaluminoborosilicate glass.
13. The dental filling and restorative material according to claim 1 or 2, further comprising a peroxide (D).
14. 3. The dental filling and restorative material according to claim 1, comprising a first material containing a peroxide (D) and a second material not containing a peroxide (D).
15. The dental filling and restorative material according to claim 14, wherein the second material comprises an organic fluorinating agent (A).
16. A kit comprising the dental filling and restorative material according to claim 1 or 2 and a tooth surface treatment material.
17. A kit comprising the dental filling and restorative material according to claim 1 or 2 and a dental adhesive.
Citation Information
Patent Citations
Multifunctional filler for dental use
JP2001139844A